Collection, handling and care of cephalopod eggs - Roger Villanueva; Anne-Sophie Darmaillacq; Michael J. Kuba; Katina Roumbedakis; Jaruwat Nabhitabhata; Eduardo Almansa; Claudia Caamal-Monsreal; Melanie Court; Ludovic Dickel; Erica D. Durante; Ali M. Elagoz; Oscar Escolar; et al. (Reviews in Fish Biology and Fisheries, 2026)
Research on cephalopod early ontogeny has significantly advanced in recent decades, including embryo organogenesis and neurogenesis and early behavioural adaptations, particularly in commercially important and coastal species. Within this context, here we compiled current knowledge on the collection, handling and care under experimental conditions and monitoring in the field of cephalopod eggs and egg masses. It covers field observations and egg collection methods, as well as laboratory incubation protocols for eggs maintained with and without maternal care. It is emphasized how abiotic and biotic factors, including temperature, salinity, oxygen and maternal condition, shape embryonic development and hatchling survival and viability. Monitoring methods for cephalopod egg masses in the wild and the effects of natural threats such as storms and predators are reviewed. Anthropogenic impacts such as pollution, fisheries and climate change are also discussed. Technological advances have enabled finer analysis of neural development as the embryo grows, while ethical considerations regarding embryonic sentience capacity and welfare conditions are becoming central to current experimental designs. Based on current knowledge, it is recommended to apply ethical considerations and the 3Rs principle (Replacement, Reduction, Refinement) for cephalopod embryos following the onset of organogenesis. Thus, a list of potential indicators of health and welfare that could be used for assessing and monitoring cephalopod embryos and hatchlings is proposed. Overall, this synthesis aims to serve as a guide for advancing egg collection and laboratory incubation methodologies, as well as adopting ethical handling protocols to improve cephalopod embryo care and quality.

Nature immersion in virtual reality has limited hypoalgesia effects for muscle pain or motor performance benefits during prescribed and self-regulated tasks - Callum A. O’Malley; David J. Harris; Sam W. Hughes; Jack E. Cottrell; Daniel Lloyd; Samuel J. Vine; Tom Arthur (European Journal of Applied Physiology, 2026)
Purpose Virtual reality (VR) reduces experimental and clinical pain, but whether these effects extend to naturally occurring muscle pain (NOMP) during exercise remains unclear. This study examined whether immersive nature-based VR attenuates NOMP and improves motor performance during prescribed and self-regulated exercise. Methods Two within-participant crossover studies were conducted involving 12 (Study 1) and 24 (Study 2) healthy participants. In Study 1, participants completed a stepped incremental cycling task to exhaustion. In Study 2, participants performed self-regulated intermittent isometric handgrip contractions at light (13/100) and strong (50/100) perceived effort. Tasks were completed under immersive VR (nature scene), two-dimensional sham, and no-intervention control conditions in pseudo-randomised, counterbalanced orders. Pain onset, NOMP intensity, perceived effort, and time to exhaustion were assessed in Study (1) Muscle pain intensity and force production were measured in Study (2) Repeated measures ANOVAs and assessed main condition effects. Results Immersive VR did not delay pain onset $$\:(p=.159)$$ , prolong time to exhaustion $$\:(p=.204)$$ , or lower perceived effort compared within sham or control conditions $$\:({p}^{{\prime\:}}s>.215)$$ . A small, yet practically meaningful, reduction in NOMP intensity occurred early during cycling $$\:({F}_{\text{2,22}}=4.518,p=.023,\:{\eta\:}_{p}^{2}=0.291[\text{0.002,0.500}\left]\right)$$ but was not sustained at later phases of the task $$\:({p}^{{\prime\:}}s . In Study 2, NOMP intensity $$\:(p=.815)$$ and force production measures $$\:({p}^{{\prime\:}}s were similar across conditions. Conclusion Nature-based immersive VR had limited effects on NOMP and motor performance. Pain types that are peripherally driven, like NOMP, may be less affected by VR interventions which target central mechanisms of pain modulation. Thus, hypoalgesia effects with VR are potentially pain-type dependent.

Intersectionality and Women’s Perceptions of Climate Change and Adaptation Among NTFP-Dependent Households in Limpopo Province, South Africa - Lloyd J. S. Baiyegunhi; Linley Chiwona-Karltun (Small-scale Forestry, 2026)
Climate change-induced weather variability, particularly changes in temperature and rainfall patterns, poses significant challenges to agroforestry systems and rural livelihoods in the tropics. Understanding how female-headed households perceive and respond to these changes is important for assessing vulnerability and designing effective adaptation strategies. However, limited empirical evidence exists on climate change perceptions and adaptation among non-timber forest product (NTFP)-dependent female-headed households in South Africa, particularly using gender-sensitive and selection-corrected analytical approaches. This study analyses climate change perceptions and adaptation strategies among 240 randomly selected NTFP-dependent female-headed households in Limpopo Province, South Africa. Guided by a gender-sensitive and intersectional perspective, the study examines how socio-economic, institutional, and livelihood-related factors shape climate perceptions and adaptation responses. A Heckman selection model was employed to account for potential sample selection bias between climate change perception and adaptation decisions. The results show that educational status, household size, NTFP collection experience, access to credit, and exposure to extreme weather events are significantly associated with climate change perceptions. Adaptation responses are significantly influenced by education, household size, NTFP collection experience, market distance, access to credit, non-NTFP income, climate information, and forestry extension services. The findings underscore the importance of context-specific and gender-responsive interventions aimed at strengthening the adaptive capacity and resilience of NTFP-dependent female-headed households in rural South Africa.

Fatal leptospirosis in southern sea otters from Central California: pathologic findings and detection of Leptospira interrogans - Margaret E. Martinez; Pádraig J. Duignan; Katherine C. Prager; Cara L. Field; Mary E. Gomes; Rinosh Mani; Lilian Carswell; Tim Tinker; Joseph Tomoleoni; Michael Murray; Ri K. Chang; James O. Lloyd-Smith; et al. (Frontiers in Marine Science, 2026)
Leptospira interrogans serovar Pomona infections cause periodic outbreaks in California sea lions (CSLs; Zalophus californianus ) and sporadic deaths in phocids. However, the frequency of infection and associated health impacts remain uncharacterized in sympatric threatened southern sea otters (SSOs; Enhydra lutris nereis ), which serve as important sentinels of coastal health. Given the broad impacts of L. interrogans on other marine mammals, our objective was to screen selected SSOs for infection, determine whether leptospirosis contributes to SSO mortality, and describe leptospiral-associated lesions. A retrospective review (2005–2025) identified 19 candidate cases that underwent detailed review, including Leptospira immunohistochemistry (IHC), serology, and polymerase chain reaction (PCR), with a special focus on renal and hepatic lesions. Kidney samples were PCR-positive for 74% (14/19) of suspected cases. For eight of these, DNA sequence-based serogroup typing detected L. interrogans serogroup Pomona. Seven of the 14 PCR-positive leptospirosis cases were classified as fatal based on positive renal IHC and moderate to severe tubulointerstitial nephritis. All fatal cases had anti- L. interrogans serovar Pomona antibody titers ≥1:25,600. The remaining seven PCR-positive cases were considered nonfatal leptospirosis due to minimal and/or unrelated renal lesions and negative IHC. Nonfatal Leptospira -infected cases ranged from seronegative to low positive (1:400) for serovar Pomona. Antibody titers for Leptospira PCR-negative cases were negative. In fatal cases, gross renal changes were often inapparent or characterized by miliary white cortical foci. Renal histologic lesions included tubulointerstitial nephritis, acute tubular necrosis, and suppurative tubulitis with intratubular bacteria, along with positive IHC staining for leptospiral antigen in the lesions. Gross hepatic changes were also inapparent in fatal cases, and histologic lesions were rare, characterized in one animal by hepatocellular dissociation and in two sea otters by limited leptospiral antigen detection by IHC. Most Leptospira -infected sea otters (71%, 10/14) stranded during higher rainfall months in California, suggesting possible land-to-sea transmission from terrestrial hosts. Given these findings, and because L. interrogans serovar Pomona infections have been confirmed in sympatric CSLs and terrestrial mammals from adjacent watersheds, a focused investigation of potential marine and terrestrial disease transmission dynamics could provide new information to reduce SSO mortalities.

Neural Network-Driven Finite Element Modeling for Estimating Knee Joint Cartilage Mechanical Responses - Mahan Nematollahi; Amir Esrafilian; Jere Lavikainen; Mika E. Mononen; Lauri Stenroth; Jari Arokoski; David J. Saxby; David G. Lloyd; Rami K. Korhonen (Annals of Biomedical Engineering, 2026)
Low-fidelity, artificial intelligence (AI)-generated approaches are increasingly used to estimate kinematics and kinetics of human movement, which are traditionally measured by high-fidelity motion capture (Mocap) approaches. However, there are no methods to study knee joint tissue mechanics using such low-fidelity approaches. To do so, we investigated knee cartilage stresses and strains using finite element (FE) models driven by both high- and low-fidelity motion capture methods. We performed subject-specific FE modeling on nine healthy participants to evaluate tissue mechanical responses by two different approaches. High-fidelity kinematic and kinetic data were obtained through motion capture and musculoskeletal modeling, respectively, whereas artificial neural networks (ANNs) were used to estimate kinetic data from low-fidelity data (e.g., subject mass, height, age, gender, static knee abduction-adduction angle, and walking speed). These data were then used as loading inputs in the knee joint FE models that were generated from magnetic resonance images. The results indicated that the high- and low-fidelity approaches provided comparable estimates of maximum principal stress, maximum shear strain, and collagen fibril strain of tibial cartilage at the first peak of knee contact force ( p > 0.05). Significant differences between the methods in the peak values of the analyzed parameters were observed at the second peak of knee contact force ( p

The ecology and evolution of cues and signals in animal interspecies cooperation - K. Dunkley; M. Cantor; A.I. Afan; D.S. Ahlibi; S.J. Allen; J. Amphaeris; S. Atkins; M.C. Attwood; K. Bankhead; C.J. Blair; J.L. Bronstein; Y.R.R. Camargo; et al. (Animal Behaviour, 2026)

Expert consensus on passive heating interventions to promote skeletal muscle strength and mass: a delphi study - Elisa Lemos; Ian B. Stewart; Patrick Rodrigues; Shawnda A. Morrison; Lee Wharton; Christopher J. Tyler; Stephen S. Cheung; Sebastian Racinais; Ralph J. F. H. Gordon; Alex Lloyd; Julien D. Périard; Katsumasa Goto; et al. (European Journal of Applied Physiology, 2026)
Purpose Passive heating has emerged as a potential non‑exercise method to support muscle strength and mass, but its application is limited by inconsistent protocols and unclear dosage and safety guidelines. This study used a Delphi methodology to establish expert consensus on key parameters for passive heating interventions targeting neuromuscular and muscle morphology outcomes. Methods An international panel of academic experts (≥ 3 peer‑reviewed publications in passive heating and neuromuscular function) completed a two‑round Delphi process. Round 1 gathered open‑ended responses on passive heating strategies, intervention targets, and safety. In Round 2, experts ranked the importance of generated statements. Consensus was defined as ≥ 70% ranking a statement as either first or second in importance. Results Eleven experts completed Round 1 and ten in Round 2. From 177 qualitative responses, 130 statements were evaluated, with 11 reaching consensus (80–100% agreement; interquartile range = 0–1). Hot‑water immersion was prioritised as the most optimal passive heating modality. Experts agreed on targeting muscle temperatures of 39–40 °C, ~ 60-minute session durations, and once‑daily exposure as key intervention parameters. Strong consensus was also reached for monitoring core temperature and cardiovascular strain (e.g., heart rate, blood pressure) to ensure participant safety. No consensus was reached on a single target population or the total intervention duration. Conclusion This Delphi study provides a consensus‑based framework outlining key parameters and safety considerations for passive heating interventions. These findings do not establish efficacy but identify priority variables to inform future experimental research and cautious translation into applied and clinical contexts.

Swimming in urban estuaries: Understanding stormwater contamination events and recovery from historical data - Simon D. Lloyd; Josef I. Bisits; Gordana Popovic; Paul Osmond; David J. Roser; Stuart J. Khan (Water Research, 2026)

Cryptic coral reef microhabitats and the functional role of brittle stars in biogenic sediment generation - D. M. de Bakker; C. T. Perry; L. de Nooijer; A. J. Ramírez-Menéndez; J. E. Lloyd Newman; F. Hale; L. Alvarez-Filip (Coral Reefs, 2026)
Recent studies have highlighted the ecological importance of cryptic habitat space on coral reefs. These microhabitats, ranging from framework cavities to intra-branch space within marine macroalgae, can harbour diverse and ecologically relevant taxa. Here we show that brittle stars, ubiquitous across such cryptic habitats (reported densities exceeding 100 ind. m −2 ), represent an important, but previously neglected, source of skeletal sediment on reefs. Reef-derived carbonate sediment is generated by a range of reef biota and represents a critical geo-ecological process, contributing to reef structural development and vertical accretion via framework infilling, and the development and maintenance of lagoonal and shoreline habitats. Our sediment production estimates are based on skeletal carbonate content data for differently sized specimens of common brittle star morphotypes, combined with field-based density assessments from widespread microhabitat types (framework cavities, sub-rubble space and intra-algal skeletal branches) on Mexican Caribbean reefs. Resulting estimates suggest that brittle stars can make substantial contributions to reef sediment production (averaging 110 g m⁻ 2 yr⁻ 1 ; 95% CI 59–161). Spine-bearing taxa contribute disproportionately due to their high skeletal mass (> 6 g in large individuals) and high abundance (accounting for over 80% of sub-rubble populations). Resultant biogenic sediments are high-Mg calcite (15.6 ± 0.1 mol% MgCO₃) and predominantly disarticulate into fine to coarse-grained sand material (125 µm–2 mm). These findings highlight the underappreciated role of brittle stars in reef carbonate cycling. With many reef systems undergoing rapid changes in benthic ecology and microhabitat space availability, identifying and characterising links to biogenic sediment sources is central to understanding future reef sediment production regimes.

Distributed optical fibre sensing in physical oceanography: emergence and future prospects - Alberto C. Naveira Garabato; Carl P. Spingys; Andrew J. Lucas; Tiago S. Dotto; Christian T. Wild; Scott W. Tyler; Ted A. Scambos; Christopher B. Kratt; Giuseppe Cappelli; Ethan F. Williams; Mariona Claret; Hannah E. Glover; et al. (Ocean Science, 2026)
Distributed optical fibre sensing (DOFS) is a technology that enables continuous, real-time measurements of a range of environmental parameters along the length of a fibre optic cable. In this article, we review the recently emerged applications of DOFS techniques in physical oceanography and offer a perspective on the technology's potential for future growth within the field. The introduction of DOFS to physical oceanography is contextualised with a brief history of the technology, which spun off primarily from the use of seafloor-laid optical fibres for telecommunications purposes. The key components and underpinning physics of a DOFS system are outlined and, on their basis, the suite of variables that are observable with DOFS are discussed. The implementation factors of DOFS, which include trade-offs between measurement accuracy and spatio-temporal resolutions and ranges, are also examined. The physical oceanographic applications of DOFS to date are then illustrated with case examples of four distinct DOFS techniques: distributed temperature sensing (DTS), which can provide ocean temperature observations; distributed static strain sensing (DSS) and distributed acoustic sensing (DAS), which are sensitive to temperature, cable strain and strain-associated variables, such as pressure and ocean velocity; and ultra-long-range observations of ocean currents with optical interferometry. The forthcoming prospects of DOFS in physical oceanography are considered, and are proposed to include new fibre optic-based approaches to sense ocean salinity and measure through the water column. We conclude with reflections on the future role of DOFS within the Global Ocean Observing System, and highlight the opportunities provided by the existing world-wide network of seafloor-laid optical fibres.

Impact of tar impurities on hydrogen recovery from coke oven gas via solid oxide electrolysis with steam - Michal M. Czachor; Christian J. Laycock; Stephen J.W. Carr; Jon Maddy; Gareth Lloyd; Alan J. Guwy (Fuel, 2026)

A horizon scan of biological conservation issues for 2026 - William J. Sutherland; Stuart H.M. Butchart; Stewart J. Clarke; Nigel R. Doar; Helen Doran; Imogen C. Douglas; Daniel J. Field; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice C. Hughes; Hermanni Kaartokallio; et al. (Trends in Ecology & Evolution, 2026)

Soil property controls on plasticiser, antioxidant and UV absorber additive degradation across a global soil gradient - Michaela K. Reay; Martine Graf; Maddy Murphy; Charlie Monkley; Perrine J. Florent; Benjamin I. Collins; Nguyen Van Hien; Tran Minh Tien; Andreia Neves Fernandes; Tapan Adhikari; Samantha Viljoen; Mona Tolba; et al. (Environmental Science and Pollution Research, 2025)
Additives in agricultural plastics can leach into the surrounding soil during use or improper disposal. Their subsequent degradation rates directly regulate whether they persist and accumulate to levels with ecotoxicological effects or are rendered benign. However, which soil properties primarily regulate the degradation of additives remains unclear (e.g. soil carbon, pH, available nutrients, microbial biomass and community structure). We assessed the degradation of the common plastic additives with different functionalities (DEHP (di(2-ethylhexyl) phthalate; plasticiser), 2-hydroxy-4-n-octyloxybenzophenone (benzophenone-12; BP12; UV stabiliser) and AO168 (tris(2,4-di- tert -butylphenyl) phosphite; antioxidant)) in soils under controlled moisture and temperature conditions over 21 days across contrasting agricultural soils from six countries across a global transect (Australia, Brazil, Egypt, India, Vietnam and the UK). DEHP followed zero-order degradation kinetics, with negligible degradation in soils with low microbial biomass. BP12 degraded fastest via first-order degradation kinetics via ether cleavage and hydroxyl loss. The degradation of DEHP and BP12 was correlated with soil microbial biomass and nitrate concentration. BP12 degradation products detected included benzophenone and benzoic acid. DEHP is degraded via β-oxidation of alkyl groups to dibutyl phthalate and diethyl phthalate and through ester hydrolysis to phthalic acid. AO168 degraded via abiotic oxidation and phosphate ester hydrolysis to 2,4-di- tert -butyl-phenol, and degradation was not well correlated with any measured soil variable. Overall, these results show that the components of additive mixtures leached into soils will degrade at different rates due to varying mechanisms and controls exerted by the soil microbial biomass. Plastic additives have differing potentials to persist in agricultural soils globally, with some likely to accumulate to levels that may impact soil function and pose an ecotoxicological threat to soil biota.

A microstructural signature of the coesite-quartz transformation: New insights from high-pressure experiments and EBSD - Rellie M. Goddard; Andrew J. Cross; Geoffrey E. Lloyd; Thomas Breithaupt; Kathryn M. Kumamoto; Brendan V. Dyck; Haiyan Chen; Andrew Parsons; Anna K. Bidgood (Earth and Planetary Science Letters, 2025)

Exploring the potential of coconut coir fiber as a biodegradable mulch: Properties, uses, processing methods, and applications - Christian Lloyd Salva; Dinah Mae B. Ordista; Philip Donald C. Sanchez; Joan Jane J. Sanchez (Bioresource Technology Reports, 2025)

Soil–climate interactions drive above-ground biomass in the Caatinga, the largest Neotropical seasonally dry tropical forest - Alexandre T. Brunello; Domingos Cardoso; Peter W. Moonlight; Ítalo A. C. Coutinho; John Cunha; Mário M. do Espírito Santo; Magna S. B. de Moura; Luciano P. de Queiroz; Rubens M. dos Santos; Tiina Särkinen; Raquel C. Miatto; Tony C. de S. Oliveira; et al. (Plant and Soil, 2025)

Proximity to Natural Habitat Is Not Consistently Associated With Pollination Services in Tropical Smallholder Farms: A Systematic Review and Meta‐Analysis - Ennia Bosshard; Mark E. Harrison; Frank van Veen; Chris J. Kettle; Nagaraja Badenahally Chikkarangappa; John E. Banks; Parthiba Basu; Quebin Bosbely Casiá‐Ajché; Bo Dalsgaard; Aditi Dutta; Eunice Enríquez; Natalia Escobedo‐Kenefic; et al. (Ecology Letters, 2025)
Proximity to natural habitat is known to enhance pollination services in large‐scale agriculture, but it remains unclear whether this holds in tropical smallholder farms. These systems are embedded in ecologically complex landscapes, central to global food security, and depend heavily on biodiversity‐derived ecosystem services. We conducted a systematic review and meta‐analysis of 35 studies assessing the relationship between distance to natural habitat and pollinator abundance, species richness, and crop fruit set in tropical smallholder farms. We found no consistent patterns in pollinator abundance and crop fruit set with increasing distance, with relationships highly variable across studies. Similarly variable, yet slightly negative, was the relationship between distance and pollinator species richness. Our findings suggest limited support for the ‘proximity to natural habitat’ hypothesis in tropical smallholder farms, indicating that the inherent complexity of these landscapes may buffer negative effects of distance on pollination. This underscores the importance of maintaining and restoring landscape complexity to sustain biodiversity and ecosystem services such as crop pollination. We also highlight the need for greater methodological consistency and publicly available raw data in future studies to strengthen the evidence base and support management strategies for safeguarding pollination services in tropical smallholder farms.

Substantiating chemical groups for read-across using molecular response profiles - Rosemary E. Barnett; Thomas N. Lawson; Claudia Rivetti; Carlos Barata; Mark T.D. Cronin; Silvia Lacorte; Gavin R. Lloyd; Ralf J.M. Weber; Matthew J. Smith; Andrew D. Southam; Adam Biales; Kara Koehrn; et al. (Regulatory Toxicology and Pharmacology, 2025)

Trawling the archives: Long-term trends in fish taxonomic and functional diversity in UK coastal community - Alice J. Clark; Caitlin Lloyd-Hall; Valentina Scarponi; J. Reuben Shipway; Ian W. Hendy; Mika Peck (Marine Environmental Research, 2025)

Robust, automated quantitation of proline in wine - Flynn T. Watson; Don Teng; Keren Bindon; Stella Kassara; Natoiya D.R. Lloyd; William S. Price; Allan Torres; Mathias Nilsson; Markus J. Herderich; Damian Espinase Nandorfy (Food Chemistry, 2025)

Origins and fluxes of gas emissions from the Central Volcanic Zone of the Andes - J. Maarten de Moor; Peter H. Barry; Alejandro Rodríguez; Felipe Aguilera; Mauricio Aguilera; Cristóbal Gonzalez; Susana Layana; Agostina Chiodi; Fredy Apaza; Pablo Masias; Christoph Kern; Jaime D. Barnes; et al. (Journal of Volcanology and Geothermal Research, 2025)

DNA gyrase-inhibitory antimicrobial anthraquinone from the endophytic Sordariomycetes fungus Diaporthe perseae - Joe Anthony H. Manzano; John Cyril D. Abanto; Beaver Andrei F. Dayo; Lloyd Christian J. Llames; Mary Grace E. Gonzaga; Simone Brogi; Allan Patrick G. Macabeo (Archives of Microbiology, 2025)

Intake of multi-component food items: A proof-of-concept study - Laura L. Wilkinson; Pamela Thompson; Alina Warren-Walker; Natalie Rouse; Louise Neilson; Sophie Vinoy; Suzanne Higgs; Amanda J. Lloyd (Appetite, 2025)

Micromolecular adaptations in Antarctic echinoderms: Overlapping roles of organic osmolytes in osmoregulation and protein stability under low temperature - Nicholas J. Barrett; Adam Burke; Royston Goodacre; Lloyd S. Peck (Science of The Total Environment, 2025)

Discovering a predictive metabolic signature of drug-induced structural cardiotoxicity in cardiac microtissues - Tara J. Bowen; Andrew R. Hall; Gavin R. Lloyd; Matthew J. Smith; Ralf J. M. Weber; Amanda Wilson; Amy Pointon; Mark R. Viant (Archives of Toxicology, 2025)
Improved prediction of drug-induced structural cardiotoxicity is required to reduce attrition driven by cardiac safety concerns in drug discovery. Omics measurements are well suited to this need, offering the potential to discover molecular signatures associated with toxicological endpoints. In addition, untargeted metabolomics can simultaneously measure xenobiotic fate within the test system. We present an extensive metabolomics study to discover a predictive metabolic signature of drug-induced structural cardiotoxicity. A human-relevant in vitro cardiac model, cardiac microtissues, were exposed to twelve xenobiotics (eight clinically labelled structural cardiotoxins and four non-cardiotoxic pharmaceuticals), each at two concentrations, for 6, 24, and 48 h. The measurements were made by direct-infusion and liquid-chromatography mass spectrometry from intracellular polar and lipid extracts, and spent culture medium, respectively. Data were used to quantify levels, and reveal the metabolic fate of the xenobiotics, and to simultaneously explore their effects on the cardiac microtissues. Xenobiotic quantification revealed free concentrations to be typically lower than nominal values, whilst discovery of xenobiotic-related features evidenced the biotransformation capacity of the microtissues. Both common and condition-specific effects of the xenobiotics on the intracellular metabolome, lipidome, and metabolic footprint were discovered. Moreover, metabolic signatures with capacity to predict structural cardiotoxicity were revealed. These included features representing several ceramides, energy metabolism intermediates, e.g. creatine, purine-related metabolites, and markers of oxidative stress, e.g. glutathione.

Seasonal occurrence and condition of leopard seals at an extralimital Sub-Antarctic Island - Michael D. Ross; Monica Leitner; W. Chris Oosthuizen; Marthán N. Bester; Rowan K. Jordaan; Michael D. Voysey; Everhard C. Conradie; Banele Dosi; Sean Evans; Kyle J. Lloyd; Zafar Monier; Jean Purdon; et al. (Polar Biology, 2025)
Leopard seals ( Hydrurga leptonyx ) occur mainly south of the Antarctic Polar Front, but immatures, in particular, seasonally move beyond this range during the austral winter and spring, typically under increased sea ice conditions. Extralimital occurrences of leopard seals can be observed at several sub-Antarctic islands where they haul out to rest. We present new records of leopard seal sightings at Marion Island, southern Indian Ocean, from 2006 to 2024 and discuss fluctuations in their seasonal and annual abundance (drawing on data collected since 1980) and body condition based on regular surveys. The eastern beaches at Marion Island were surveyed every 7–10 days while the western beaches were visited monthly. Observed leopard seals were photographed and given a body condition score based on the visibility of bony protrusions. From 2006 to 2024, we identified 35 presumed unique immature leopard seals between July and November, with a peak in September, all being immatures. Individuals to which we could assign body condition scores were either in good or excellent condition. This contrasted with the prevailing hypothesis that leopard seal body condition deteriorates with decreasing latitude. However, we could not determine whether this was because of an actual shift in body condition or because we used a different scoring system from other studies. We recommend adopting a standardised scoring system for visually estimating pinniped body condition and a global repository to monitor leopard seal haul-outs. As an apex predator, leopard seals may be important indicators in Antarctic and sub-Antarctic ecosystems, and monitoring changes in their distribution and body condition may indicate environmental and biological changes in these remote regions.

Conservation changed but not divided - Sam A. Reynolds; Sara Beery; Neil Burgess; Mark Burgman; Stuart H.M. Butchart; Steven J. Cooke; David Coomes; Finn Danielsen; Enrico Di Minin; América Paz Durán; Amy Hinsley; Sadiq Jaffer; et al. (Trends in Ecology & Evolution, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

The economic value of human-honeyguide mutualism in Reserva Especial do Niassa, Moçambique - Jessica E.M. van der Wal; Celestino Dauda; David J. Lloyd-Jones; Horácio Murico; Colleen M. Begg; Keith S. Begg; Agostinho A. Jorge; Claire N. Spottiswoode (Ecosystem Services, 2025)

Evaluating the acclimation capacity of two keystone Antarctic echinoderms to coastal freshening - Nicholas J. Barrett; Elizabeth M. Harper; Lloyd S. Peck (Science of The Total Environment, 2025)

Microbial sulfate reduction regulated by relative sea level change in a Pleistocene – Holocene sedimentary record: Insights from Loch Duart, Scotland, UK - L.G. Podrecca; A.L. Masterson; M.T. Hurtgen; J. Taylor; J.M. Lloyd; D. Selby; B.B. Sageman (Chemical Geology, 2025)

The potential for AI to revolutionize conservation: a horizon scan - Sam A. Reynolds; Sara Beery; Neil Burgess; Mark Burgman; Stuart H.M. Butchart; Steven J. Cooke; David Coomes; Finn Danielsen; Enrico Di Minin; América Paz Durán; Francis Gassert; Amy Hinsley; et al. (Trends in Ecology & Evolution, 2025)

Carbon, nitrogen, and noble gas isotopes reveal deep volatile signatures in thermal springs in the Central Volcanic Zone (CVZ) of the Andes - PH Barry; JM de Moor; MW Broadley; AM Seltzer; DV Bekaert; K Patil; CGE Bartels; ED Young; BE Longworth; B Barosa; A Bastianoni; D Bastoni; et al. (Earth and Planetary Science Letters, 2025)

The Influence of Structural Design on the Hydrodynamics of Floating Offshore Wind Turbine Platforms - Nilotpal Dhar; Charlie J. Lloyd; John Walker; Robert M. Dorrell (Journal of Marine Science and Engineering, 2025)
Floating offshore wind turbine (FOWT) platforms are subject to a wide range of hydrodynamic loading and dynamic movement, making hydrodynamic force evaluation difficult. Amongst various floating platforms, submersible platforms are structurally complex, with multiple members held together by cross-braces. The influence of these members on hydrodynamic loading is poorly understood. An investigation of the effect of these members on loads is essential to optimise the design of FOWT platforms, mooring systems, and protective coatings, leading to a reduction in construction and maintenance costs. This paper numerically investigates the effect of structural members on the forces acting on a static semi-submersible platform in a unidirectional current flow of Reynolds number (Re) ranging from 2000 to 200,000, based on structural diameter and tidal velocity. The OC4 semi-submersible is chosen as the baseline platform. For each Re, this study is divided into three stages, such that in each stage, the number of members increased. These stages are as follows: (1) a finite cylinder (FC), (2) a finite cylinder with a heave plate (FCHP), (3) three cylinders with heave plates (TCHP) in an equilateral triangle arrangement, and (4) the OC4 semi-sub. The drag coefficient (C¯d) increases with increasing structural members and weakly varies with increasing Re. However, the viscous drag coefficient (C¯f) decreases with increasing Re, and a reverse trend is seen in the case of the pressure drag coefficient (C¯p), with pressure drag dominating over friction drag. Further, the contribution of individual members is observed to vary with Re. The contribution of cylinders towards C¯d is higher than heave plates, showing that contributions directly depend on the aspect ratio of members. In the case of TCHP and OC4, the contribution of the rear members is higher than that of the leading members due to the strong wake effect of the former. Also, the braces and pontoons of OC4 have contributed substantially towards total C¯d, unlike the central cylinder, which has experienced low drag due to the wake effect of the front cylinder and heave plate. Also, flow visualisation has shown vortex cores, and recirculating flows in the near wake of the cylinders and under the heave plates. Recirculation zones under the heave plates lead to vertical pressure on the structures. This vertical pressure increases with the number of structural members and the vertical pressure coefficient (C¯v), varying with Re due to three-dimensionality in the wake. Further, this pressure varies across the bottom surfaces of structures. Analyses of the streamwise pressure coefficient have shown it is highest on the front surfaces of cylinders. The highest friction is on the top and sides of the heave plates, and there is considerable friction on the sides of the cylinder.

A horizon scan of biological conservation issues for 2025 - William J. Sutherland; Peter N.M. Brotherton; Holly M. Butterworth; Stewart J. Clarke; Tammy E. Davies; Nigel Doar; Nafeesa Esmail; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice C. Hughes; Jonathan Hughes; et al. (Trends in Ecology & Evolution, 2025)

Exploring the impact of carbohydrate chain length on binding affinity with lectin-a protein from common edible mushroom (Agaricus bisporus) - Mengya He; Lloyd Condict; Samantha J. Richardson; Charles S. Brennan; Stefan Kasapis (Food Hydrocolloids, 2025)

Measuring the association between the opening of a new multi-national restaurant with young people's eating behaviours - Helen J. Moore; Claire L. O'Malley; Scott Lloyd; Fatemeh Eskandari; Kelly Rose; Mark Butler; Tim G. Townshend; Heather Brown; Daniel Clarkson; Amelia A. Lake (Appetite, 2024)

Interpretation of river water quality data is strongly controlled by measurement time and frequency - Inge Elfferich; Elizabeth A. Bagshaw; Rupert G. Perkins; Penny J. Johnes; Christopher A. Yates; Charlotte E.M. Lloyd; Michael J. Bowes; Sarah J. Halliday (Science of The Total Environment, 2024)

On the origin of Holocene sea-level transgressions in formerly glaciated regions - Samuel J. Chester; Jacqueline Austermann; William J. D’Andrea; Andrew J. Lloyd; Roger C. Creel (Quaternary Science Reviews, 2024)

Characterisation of dissolved organic matter in two contrasting arsenic-prone sites in Kandal Province, Cambodia - Oliver C. Moore; Amy D. Holt; Laura A. Richards; Amy M. McKenna; Robert G.M. Spencer; Dan J. Lapworth; David A. Polya; Jonathan R. Lloyd; Bart E. van Dongen (Organic Geochemistry, 2024)

Recreational hot springs as environmental reservoir of potential multidrug-resistant pathogens - Matteo Selci; Monica Correggia; Angelina Cordone; Marco Guida; Grazia Marina Quero; Roberta Piredda; Costantino Vetriani; Carlos Ramirez; Karen G. Lloyd; J. Maarten de Moor; Peter H. Barry; Matthew O. Schrenk; et al. (Environmental Research, 2024)

Weak paleointensities from 1.6 Ga Greenland dykes: Further evidence for a billion-year period of paleomagnetic dipole low during the Paleoproterozoic - Simon J. Lloyd; Andrew J. Biggin; Henry Halls; Steve Denyszyn (Earth and Planetary Science Letters, 2024)

Tracing the orogenic sulfur cycle in the Andes using stable isotope composition of dissolved sulfate in thermal springs - Tyler A. Grambling; Dennis L. Newell; Karen G. Lloyd; Coleman D. Hiett; Heather Upin; Peter H. Barry; Donato Giovannelli; J. Maarten de Moor; Agostina Chiodi; Gerdhard L. Jessen; Jenny M. Blamey; Anna Szynkiewicz (Chemical Geology, 2024)

Nitrous oxide and methane fluxes from plasma-treated pig slurry applied to winter wheat - I. L. Lloyd; R. P. Grayson; M. V. Galdos; R. Morrison; P. J. Chapman (Nutrient Cycling in Agroecosystems, 2024)
The use of livestock waste as an organic fertiliser releases significant greenhouse gas emissions, exacerbating climate change. Innovative fertiliser management practices, such as treating slurry with plasma induction, have the potential to reduce losses of carbon and nitrogen to the environment. The existing research on the effectiveness of plasma-treated slurry at reducing nitrous oxide (N 2 O) and methane (CH 4 ) emissions, however, is not comprehensive, although must be understood if this technology is to be utilised on a large scale. A randomised block experiment was conducted to measure soil fluxes of N 2 O and CH 4 from winter wheat every two hours over an 83-day period using automated chambers. Three treatments receiving a similar amount of plant-available N were used: (1) inorganic fertiliser (IF); (2) pig slurry combined with inorganic fertiliser (PS); (3) plasma-treated pig slurry combined with inorganic fertiliser (TPS). Cumulative N 2 O fluxes from TPS (1.14 g N m −2 ) were greater than those from PS (0.32 g N m −2 ) and IF (0.13 g N m −2 ). A diurnal pattern in N 2 O fluxes was observed towards the end of the experiment for all treatments, and was driven by increases in water-filled pore space and photosynthetically active radiation and decreases in air temperature. Cumulative CH 4 fluxes from PS (3.2 g C m −2 ) were considerably greater than those from IF (− 1.4 g C m −2 ) and TPS (− 1.4 g C m −2 ). The greenhouse gas intensity of TPS (0.2 g CO 2 -eq kg grain −1 ) was over twice that of PS (0.07 g CO 2 -eq kg grain −1 ) and around six times that of IF (0.03 g CO 2 -eq kg grain −1 ). Although treating pig slurry with plasma induction considerably reduced CH 4 fluxes from soil, it increased N 2 O emissions, resulting in higher non-CO 2 emissions from this treatment. Life-cycle analysis will be required to evaluate whether the upstream manufacturing and transport emissions associated with inorganic fertiliser usage are outweighed by the emissions observed following the application of treated pig slurry to soil.

Nundorite: a geological oddity of critical minerals significance from the Mount Arrowsmith Volcanics, northwestern NSW - L. Y. Johns-Mead; C. Spandler; J. C. Lloyd (Australian Journal of Earth Sciences, 2024)

Depth-specific distribution of bacterial MAGs in permafrost active layer in Ny Ålesund, Svalbard (79°N) - Katie Sipes; Joy Buongiorno; Andrew D. Steen; Andrey A. Abramov; Chukwufumnanya Abuah; Samantha L. Peters; Richard J. Gianonne; Robert L. Hettich; Julia Boike; Sarahi L. Garcia; Tatiana A. Vishnivetskaya; Karen G. Lloyd (Systematic and Applied Microbiology, 2024)

The Current State of Biotransformation Science – Industry Survey of In Vitro and In Vivo Practices, Clinical Translation, and Future Trends - John P. Savaryn; Kevin Coe; Matthew A. Cerny; Kevin Colizza; Patricia Moliner; Lloyd King; Bin Ma; Jim Atherton; Adam Auclair; Mark T. Cancilla; Marsha Eno; Ulrik Jurva; et al. (Pharmaceutical Research, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Proteome profiling of lumichrome-treated Arabidopsis thaliana suggests that various regulatory mechanisms mediate enhanced photosynthesis and plant growth - Motlalepula Pholo-Tait; Waltraud X. Schulze; Saleh Alseekh; Alex J. Valentine; Nicholas C. Le Maitre; James R. Lloyd; Jens Kossmann; Paul N. Hills (South African Journal of Botany, 2024)

Multi-omics bioactivity profile-based chemical grouping and read-across: a case study with Daphnia magna and azo dyes - Hanna Gruszczynska; Rosemary E. Barnett; Gavin R. Lloyd; Ralf J. M. Weber; Thomas N. Lawson; Jiarui Zhou; Elena Sostare; John K. Colbourne; Mark R. Viant (Archives of Toxicology, 2024)
Grouping/read-across is widely used for predicting the toxicity of data-poor target substance(s) using data-rich source substance(s). While the chemical industry and the regulators recognise its benefits, registration dossiers are often rejected due to weak analogue/category justifications based largely on the structural similarity of source and target substances. Here we demonstrate how multi-omics measurements can improve confidence in grouping via a statistical assessment of the similarity of molecular effects. Six azo dyes provided a pool of potential source substances to predict long-term toxicity to aquatic invertebrates ( Daphnia magna ) for the dye Disperse Yellow 3 (DY3) as the target substance. First, we assessed the structural similarities of the dyes, generating a grouping hypothesis with DY3 and two Sudan dyes within one group. Daphnia magna were exposed acutely to equi-effective doses of all seven dyes (each at 3 doses and 3 time points), transcriptomics and metabolomics data were generated from 760 samples. Multi-omics bioactivity profile-based grouping uniquely revealed that Sudan 1 (S1) is the most suitable analogue for read-across to DY3. Mapping ToxPrint structural fingerprints of the dyes onto the bioactivity profile-based grouping indicated an aromatic alcohol moiety could be responsible for this bioactivity similarity. The long-term reproductive toxicity to aquatic invertebrates of DY3 was predicted from S1 (21-day NOEC, 40 µg/L). This prediction was confirmed experimentally by measuring the toxicity of DY3 in D. magna . While limitations of this ‘omics approach are identified, the study illustrates an effective statistical approach for building chemical groups.

The deglacial history of 79N glacier and the Northeast Greenland Ice Stream - David H. Roberts; Timothy P. Lane; Richard S. Jones; Michael J. Bentley; Christopher M. Darvill; Angel Rodes; James A. Smith; Stewart S.R. Jamieson; Brice R. Rea; Derek Fabel; Delia Gheorghiu; Allan Davidson; et al. (Quaternary Science Reviews, 2024)

Past and future river bank trend assessment of lower Cagayan River, Philippines - Alvin John B. Felipe; Lanie A. Alejo; Rafael J. Padre; Jeoffrey Lloyd R. Bareng (Environment, Development and Sustainability, 2024)

Predicting recreational water quality and public health safety in urban estuaries using Bayesian Networks - Simon D. Lloyd; Guido Carvajal; Meredith Campey; Nerida Taylor; Paul Osmond; David J. Roser; Stuart J. Khan (Water Research, 2024)

Remeasuring the influence of ageing on heat-related mortality in Spain, 1980 to 2018 - Simon J. Lloyd; Erich Striessnig; Hicham Achebak; Shakoor Hajat; Raya Muttarak; Marcos Quijal-Zamorano; Silvia Rizzi; Constanza Vielma; Joan Ballester (Environmental Research, 2024)

Demonstrating the reliability of in vivo metabolomics based chemical grouping: towards best practice - Mark R. Viant; E. Amstalden; T. Athersuch; M. Bouhifd; S. Camuzeaux; D. M. Crizer; P. Driemert; T. Ebbels; D. Ekman; B. Flick; V. Giri; M. Gómez-Romero; et al. (Archives of Toxicology, 2024)
While grouping/read-across is widely used to fill data gaps, chemical registration dossiers are often rejected due to weak category justifications based on structural similarity only. Metabolomics provides a route to robust chemical categories via evidence of shared molecular effects across source and target substances. To gain international acceptance, this approach must demonstrate high reliability, and best-practice guidance is required. The MetAbolomics ring Trial for CHemical groupING (MATCHING), comprising six industrial, government and academic ring-trial partners, evaluated inter-laboratory reproducibility and worked towards best-practice. An independent team selected eight substances (WY-14643, 4-chloro-3-nitroaniline, 17α-methyl-testosterone, trenbolone, aniline, dichlorprop-p, 2-chloroaniline, fenofibrate); ring-trial partners were blinded to their identities and modes-of-action. Plasma samples were derived from 28-day rat tests (two doses per substance), aliquoted, and distributed to partners. Each partner applied their preferred liquid chromatography–mass spectrometry (LC–MS) metabolomics workflows to acquire, process, quality assess, statistically analyze and report their grouping results to the European Chemicals Agency, to ensure the blinding conditions of the ring trial. Five of six partners, whose metabolomics datasets passed quality control, correctly identified the grouping of eight test substances into three categories, for both male and female rats. Strikingly, this was achieved even though a range of metabolomics approaches were used. Through assessing intrastudy quality-control samples, the sixth partner observed high technical variation and was unable to group the substances. By comparing workflows, we conclude that some heterogeneity in metabolomics methods is not detrimental to consistent grouping, and that assessing data quality prior to grouping is essential. We recommend development of international guidance for quality-control acceptance criteria. This study demonstrates the reliability of metabolomics for chemical grouping and works towards best-practice.

Overprinting orogenic events, ductile extrusion and strain partitioning during Caledonian transpression, NW Mainland Shetland - Timothy B. Armitage; Robert E. Holdsworth; Robin A. Strachan; Edward D. Dempsey; Richard J. Walker; Diana T. Alvarez-Ruiz; Geoffrey E. Lloyd (Journal of Structural Geology, 2024)

A supervised parallel optimisation framework for metaheuristic algorithms - Eugenio J. Muttio; Wulf G. Dettmer; Jac Clarke; Djordje Perić; Zhaoxin Ren; Lloyd Fletcher (Swarm and Evolutionary Computation, 2024)

A horizon scan of global biological conservation issues for 2024 - William J. Sutherland; Craig Bennett; Peter N.M. Brotherton; Stuart H.M. Butchart; Holly M. Butterworth; Stewart J. Clarke; Nafeesa Esmail; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice C. Hughes; Jennifer James; et al. (Trends in Ecology & Evolution, 2024)

Soil δ15N spatial distribution is primarily shaped by climatic patterns in the semiarid Caatinga, Northeast Brazil - Alexandre T. Brunello; Gabriela B. Nardoto; Fábio Luís S. Santos; João Paulo Sena-Souza; Carlos A.N. Quesada; Jonathan J. Lloyd; Tomas F. Domingues (Science of The Total Environment, 2024)

Molecular characterization of interactions between lectin - a protein from common edible mushroom (Agaricus bisporus) - and dietary carbohydrates - Mengya He; Lloyd Condict; Samantha J. Richardson; Charles S. Brennan; Stefan Kasapis (Food Hydrocolloids, 2024)

Climate and human stressors on global penguin hotspots: Current assessments for future conservation - Míriam Gimeno; Joan Giménez; Andre Chiaradia; Lloyd S. Davis; Philip J. Seddon; Yan Ropert‐Coudert; Ryan R. Reisinger; Marta Coll; Francisco Ramírez (Global Change Biology, 2024)
As charismatic and iconic species, penguins can act as “ambassadors” or flagship species to promote the conservation of marine habitats in the Southern Hemisphere. Unfortunately, there is a lack of reliable, comprehensive, and systematic analysis aimed at compiling spatially explicit assessments of the multiple impacts that the world's 18 species of penguin are facing. We provide such an assessment by combining the available penguin occurrence information from Global Biodiversity Information Facility (>800,000 occurrences) with three main stressors: climate‐driven environmental changes at sea, industrial fisheries, and human disturbances on land. Our analyses provide a quantitative assessment of how these impacts are unevenly distributed spatially within species' distribution ranges. Consequently, contrasting pressures are expected among species, and populations within species. The areas coinciding with the greatest impacts for penguins are the coast of Perú, the Patagonian Shelf, the Benguela upwelling region, and the Australian and New Zealand coasts. When weighting these potential stressors with species‐specific vulnerabilities, Humboldt ( Spheniscus humboldti ), African ( Spheniscus demersus ), and Chinstrap penguin ( Pygoscelis antarcticus ) emerge as the species under the most pressure. Our approach explicitly differentiates between climate and human stressors, since the more achievable management of local anthropogenic stressors (e.g., fisheries and land‐based threats) may provide a suitable means for facilitating cumulative impacts on penguins, especially where they may remain resilient to global processes such as climate change. Moreover, our study highlights some poorly represented species such as the Northern Rockhopper ( Eudyptes moseleyi ), Snares ( Eudyptes robustus ), and Erect‐crested penguin ( Eudyptes sclateri ) that need internationally coordinated efforts for data acquisition and data sharing to understand their spatial distribution properly.

Towards linking slab window geodynamics with the geophysical and geochemical signature of the upper mantle - Jorge Sanhueza; Gonzalo Yáñez; W. Roger Buck; Amol Dayanand Sawant; Jaime Araya Vargas; Andrew J. Lloyd (Earth and Planetary Science Letters, 2023)

Copper bioreduction and nanoparticle synthesis by an enrichment culture from a former copper mine - Richard L. Kimber; Gretta Elizondo; Klaudia Jedyka; Christopher Boothman; Rongsheng Cai; Heath Bagshaw; Sarah J. Haigh; Victoria S. Coker; Jonathan R. Lloyd (Environmental Microbiology, 2023)
Microorganisms can facilitate the reduction of Cu 2+ , altering its speciation and mobility in environmental systems and producing Cu‐based nanoparticles with useful catalytic properties. However, only a few model organisms have been studied in relation to Cu 2+ bioreduction and little work has been carried out on microbes from Cu‐contaminated environments. This study aimed to enrich for Cu‐resistant microbes from a Cu‐contaminated soil and explore their potential to facilitate Cu 2+ reduction and biomineralisation from solution. We show that an enrichment grown in a Cu‐amended medium, dominated by species closely related to Geothrix fermentans, Azospira restricta and Cellulomonas oligotrophica , can reduce Cu 2+ with subsequent precipitation of Cu nanoparticles. Characterisation of the nanoparticles with (scanning) transmission electron microscopy, energy‐dispersive x‐ray spectroscopy and electron energy loss spectroscopy supports the presence of both metallic Cu(0) and S‐rich Cu(I) nanoparticles. This study provides new insights into the diversity of microorganisms capable of facilitating copper reduction and highlights the potential for the formation of distinct nanoparticle phases resulting from bioreduction or biomineralisation reactions. The implications of these findings for the biogeochemical cycling of copper and the potential biotechnological synthesis of commercially useful copper nanoparticles are discussed.

Occurrence and sources of microplastics on Arctic beaches: Svalbard - Tesni Lloyd-Jones; Jonathan J. Dick; Timothy P. Lane; Eoghan M. Cunningham; Konstadinos Kiriakoulakis (Marine Pollution Bulletin, 2023)

Development of an isocaloric test food set with multi-component and control ice-creams - Laura L. Wilkinson; Pamela Thompson; Odin Morón-García; Alina Warren-Walker; Amanda J. Lloyd (Appetite, 2023)

P24-26: Metabolomics-based chemical grouping – a robust and reproducible tool enabling read-across - H. Kamp; E. Amstalden; T. Athersuch; M. Bouhifd; T. Ebbels; D. Ekman; V. Haake; A. Kende; P. Leonards; G. Lloyd; J. Mosley; C. Sands; et al. (Toxicology Letters, 2023)

Density-related reproductive costs and natal conditions predict male life history in a highly polygynous mammal - Kyle J. Lloyd; W. Chris Oosthuizen; Jay J. Rotella; Marthán N. Bester; P.J.Nico de Bruyn (Animal Behaviour, 2023)

Comprehensive ECG reference intervals in C57BL/6N substrains provide a generalizable guide for cardiac electrophysiology studies in mice - Manuela A. Oestereicher; Janine M. Wotton; Shinya Ayabe; Ghina Bou About; Tsz Kwan Cheng; Jae-Hoon Choi; Dave Clary; Emily M. Dew; Lahcen Elfertak; Alain Guimond; Hamed Haseli Mashhadi; Jason D. Heaney; et al. (Mammalian Genome, 2023)
Reference ranges provide a powerful tool for diagnostic decision-making in clinical medicine and are enormously valuable for understanding normality in pre-clinical scientific research that uses in vivo models. As yet, there are no published reference ranges for electrocardiography (ECG) in the laboratory mouse. The first mouse-specific reference ranges for the assessment of electrical conduction are reported herein generated from an ECG dataset of unprecedented scale. International Mouse Phenotyping Consortium data from over 26,000 conscious or anesthetized C57BL/6N wildtype control mice were stratified by sex and age to develop robust ECG reference ranges. Interesting findings include that heart rate and key elements from the ECG waveform (RR-, PR-, ST-, QT-interval, QT corrected, and QRS complex) demonstrate minimal sexual dimorphism. As expected, anesthesia induces a decrease in heart rate and was shown for both inhalation (isoflurane) and injectable (tribromoethanol) anesthesia. In the absence of pharmacological, environmental, or genetic challenges, we did not observe major age-related ECG changes in C57BL/6N-inbred mice as the differences in the reference ranges of 12-week-old compared to 62-week-old mice were negligible. The generalizability of the C57BL/6N substrain reference ranges was demonstrated by comparison with ECG data from a wide range of non-IMPC studies. The close overlap in data from a wide range of mouse strains suggests that the C57BL/6N-based reference ranges can be used as a robust and comprehensive indicator of normality. We report a unique ECG reference resource of fundamental importance for any experimental study of cardiac function in mice.

Determination of specific lethal heat treatment parameters for pests associated with wood products using the Humble water bath - M. K. Noseworthy; L. M. Humble; T. J. Souque; E. P. John; J. Roberts; C. R. Lloyd; E. A. Allen (Journal of Pest Science, 2023)
Heat treatment is an effective sanitization method used for over half a century to reduce the risk of transporting pests associated with wood products. The determination of precise lethal heat treatment parameters for pests is critical for the development of globally harmonized plant protection regulatory treatment policies. Separation of heat treatment dose (time and temperature) from the factors associated with the method of heat application (delivery) and variables associated with wood characteristics allows for universal agreement on lethal dose and promotes efficient development of treatment schedule guidance. The Humble water bath is an effective and carefully calibrated heat treatment apparatus designed to test the effects of heat and determine lethal temperature doses. Specifications for building this apparatus and experimental treatment parameters are described. To demonstrate the capacities of the water bath apparatus, the effect of heat on a non-indigenous wood-boring beetle, Anisandrus dispar, is reported using heat-ramp schedules similar to industrial kiln heating applications. Adult A. dispar tested in vitro, did not survive 50 °C treatment temperature for 15 min time duration.

Electrocardiogram to Determine Mitral and Aortic Valve Opening and Closure - M. Rifqi Aufan; Zachary T. Jost; Neal J. Miller; Oleg F. Sharifov; Himanshu Gupta; Gilbert J. Perry; J. Michael Wells; Thomas S. Denney; Steven G. Lloyd (Cardiovascular Engineering and Technology, 2023)

Prioritizing species conservation programs based on IUCN Green Status and estimates of cost‐sharing potential - Natasha A. Lloyd; Laura M. Keating; Alyssa J. Friesen; Dylan M. Cole; Jana M. McPherson; H. Resit Akçakaya; Axel Moehrenschlager (Conservation Biology, 2023)
Over 1 million species around the world are at risk of extinction, and conservation organizations have to decide where to invest their limited resources. Cost‐effectiveness can be increased by leveraging funding opportunities and increasing collaborative partnerships to achieve shared conservation goals. We devised a structured decision‐making framework to prioritize species’ conservation programs based on a cost–benefit analysis that takes collaborative opportunities into account in an examination of national and global conservation return on investment. Conservation benefit is determined by modifying the novel International Union for the Conservation of Nature Green Status for Species to provide an efficient, high‐level measure that is comparable among species, even with limited information and time constraints. We applied this prioritization approach to the Wilder Institute/Calgary Zoo, Canada, a nonprofit organization seeking to increase the number of species it assists with conservation translocations. We sought to identify and prioritize additional species’ programs for which conservation translocation expertise and actions could make the most impact. Estimating the likelihood of cost‐sharing potential enabled total program cost to be distinguished from costs specific to the organization. Comparing a benefit‐to‐cost ratio on different geographic scales allowed decision makers to weigh alternative options for investing in new species’ programs in a transparent and effective manner. Our innovative analysis aligns with general conservation planning frameworks and can be adapted for any organization.

To den or not to den. Contributions to the taphonomic history of the Early Pleistocene site of Venta Micena 4 (Orce, Guadix-Baza Basin) - Jose Yravedra Sainz de los Terreros; Carmen Luzón; Jose A. Solano; Gonzalo J. Linares-Matas; Verónica Estaca-Gomez; Juan José Rodríguez-Alba; Lloyd A. Courtenay; Darío Herranz-Rodrigo; Alexia Serrano-Ramos; José Cámara; Juha Saarinen; Christian Sánchez-Bandera; et al. (Quaternary Science Reviews, 2023)

Exploring the inhibitory mechanism of p-coumaric acid on α-amylase via multi-spectroscopic analysis, enzymatic inhibition assay and molecular docking - Yanyi Huang; Lloyd Condict; Samantha J. Richardson; Charles Stephen Brennan; Stefan Kasapis (Food Hydrocolloids, 2023)

Disparities in economic values for nature-based activities in Canada - Danielle S. Spence; Corinne J. Schuster-Wallace; Patrick Lloyd-Smith (Ecological Economics, 2023)

Derivation of metabolic point of departure using high-throughput in vitro metabolomics: investigating the importance of sampling time points on benchmark concentration values in the HepaRG cell line - Julia M. Malinowska; Taina Palosaari; Jukka Sund; Donatella Carpi; Ralf J. M. Weber; Gavin R. Lloyd; Maurice Whelan; Mark R. Viant (Archives of Toxicology, 2023)
Amongst omics technologies, metabolomics should have particular value in regulatory toxicology as the measurement of the molecular phenotype is the closest to traditional apical endpoints, whilst offering mechanistic insights into the biological perturbations. Despite this, the application of untargeted metabolomics for point-of-departure (POD) derivation via benchmark concentration (BMC) modelling is still a relatively unexplored area. In this study, a high-throughput workflow was applied to derive PODs associated with a chemical exposure by measuring the intracellular metabolome of the HepaRG cell line following treatment with one of four chemicals (aflatoxin B 1 , benzo[a]pyrene, cyclosporin A, or rotenone), each at seven concentrations (aflatoxin B 1 , benzo[a]pyrene, cyclosporin A: from 0.2048 μM to 50 μM; rotenone: from 0.04096 to 10 μM) and five sampling time points (2, 6, 12, 24 and 48 h). The study explored three approaches to derive PODs using benchmark concentration modelling applied to single features in the metabolomics datasets or annotated metabolites or lipids: (1) the 1st rank-ordered unannotated feature, (2) the 1st rank-ordered putatively annotated feature (using a recently developed HepaRG-specific library of polar metabolites and lipids), and (3) 25th rank-ordered feature, demonstrating that for three out of four chemical datasets all of these approaches led to relatively consistent BMC values, varying less than tenfold across the methods. In addition, using the 1st rank-ordered unannotated feature it was possible to investigate temporal trends in the datasets, which were shown to be chemical specific. Furthermore, a possible integration of metabolomics-driven POD derivation with the liver steatosis adverse outcome pathway (AOP) was demonstrated. The study highlights that advances in technologies enable application of in vitro metabolomics at scale; however, greater confidence in metabolite identification is required to ensure PODs are mechanistically anchored.

The National Conference on Health Disparities Student Research Forum - Marvella E. Ford; Angela M. Malek; Erica Martino; Latecia Abraham-Hilaire; Oluwole Ariyo; Dana Burshell; Gloria Callwood; Laura Campbell; Kimberly Cannady; Courtney Chavis; Brittney Crawford; Andie Edwards; et al. (Journal of Cancer Education, 2023)
The annual National Conference on Health Disparities (NCHD) was launched in 2000. It unites health professionals, researchers, community leaders, and government officials, and is a catalyzing force in developing policies, research interventions, and programs that address prevention, social determinants, health disparities, and health equity. The NCHD Student Research Forum (SRF) was established in 2011 at the Medical University of South Carolina to build high-quality biomedical research presentation capacity in primarily underrepresented undergraduate and graduate/professional students. This paper describes the unique research training and professional development aspects of the NCHD SRF. These include guidance in abstract development, a webinar on presentation techniques and methods, a vibrant student-centric conference, and professional development workshops on finding a mentor and locating scholarship/fellowship funding, networking, and strategies for handling ethical issues in research with mentors. Between 2011 and 2018, 400 undergraduate and graduate/professional students participated in the NCHD SRF. Most students were women (80.5%). Approximately half were African American or black (52.3%), 18.0% were white, and 21.3% were of Hispanic/Latinx ethnicity. The NCHD SRF is unique in several ways. First, it provides detailed instructions on developing a scientific abstract, including content area examples. Second, it establishes a mandatory pre-conference training webinar demonstrating how to prepare a scientific poster. Third, it works with the research mentors, faculty advisors, department chairs, and deans to help identify potential sources of travel funding for students with accepted abstracts. These features make the NCHD SRF different from many other conferences focused on students’ scientific presentations.

A global biological conservation horizon scan of issues for 2023 - William J. Sutherland; Craig Bennett; Peter N.M. Brotherton; Holly M. Butterworth; Mick N. Clout; Isabelle M. Côté; Jason Dinsdale; Nafeesa Esmail; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice Hughes; et al. (Trends in Ecology & Evolution, 2023)

Episodic Ataxia Type 1: Natural History and Effect on Quality of Life - Tracey D. Graves; Robert C. Griggs; Brian N. Bundy; Joanna C. Jen; Robert W. Baloh; Michael G. Hanna; Joanna J. Jen; Anthony A. Amato; Richard J. Barohn; Angelika F. Hahn; Kimberly Hart; Barbara Herr; et al. (The Cerebellum, 2022)
Episodic ataxia type 1 (EA1) is a rare autosomal potassium channelopathy, due to mutations in KCNA1 . Patients have childhood onset of intermittent attacks of ataxia, dizziness or imbalance. In order to quantify the natural history of EA1, its effect on quality of life and in preparation for future clinical trials, we set up an international multi-centre study of EA1. We recruited thirty-three participants with EA1: twenty-three completed 1-year follow-up and eighteen completed 2-year follow-up. There was very little accumulation of disability or impairment over the course of the 2 years of the study. The outcome measures of ataxia (SARA and functional rating of ataxia) and the activities of daily living scale were largely stable over time. Self-reported health-related quality of life (SF-36) scores were lower across all domains than controls, in keeping with a chronic condition. Physical subdomain scores appeared to deteriorate over time, which seems to be driven by the female participants in the study. This is an interesting finding and warrants further study. Attacks of EA1 reported by participants in real time via an interactive voice response system showed that symptoms were not stereotyped; however, attack duration and frequency was stable between individuals. This large prospective study is the first ever completed in subjects with EA1. We document the natural history of the disorder over 2 years. These data will enable the development of outcome measures for clinical trials of treatment.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Mechanism underpinning the sharpening of orientation and spatial frequency selectivities in the tree shrew (Tupaia belangeri) primary visual cortex - Yamni S. Mohan; Sivaram Viswanathan; Jaikishan Jayakumar; Errol K. J. Lloyd; Trichur R. Vidyasagar (Brain Structure and Function, 2022)

A trait‐based model ensemble approach to design rice plant types for future climate - Livia Paleari; Tao Li; Yubin Yang; Lloyd T. Wilson; Toshihiro Hasegawa; Kenneth J. Boote; Samuel Buis; Gerrit Hoogenboom; Yujing Gao; Ermes Movedi; Françoise Ruget; Upendra Singh; et al. (Global Change Biology, 2022)
Crop models are powerful tools to support breeding because of their capability to explore genotype × environment×management interactions that can help design promising plant types under climate change. However, relationships between plant traits and model parameters are often model specific and not necessarily direct, depending on how models formulate plant morphological and physiological features. This hinders model application in plant breeding. We developed a novel trait‐based multi‐model ensemble approach to improve the design of rice plant types for future climate projections. We conducted multi‐model simulations targeting enhanced productivity, and aggregated results into model‐ensemble sets of phenotypic traits as defined by breeders rather than by model parameters. This allowed to overcome the limitations due to ambiguities in trait‐parameter mapping from single modelling approaches. Breeders' knowledge and perspective were integrated to provide clear mapping from designed plant types to breeding traits. Nine crop models from the AgMIP‐Rice Project and sensitivity analysis techniques were used to explore trait responses under different climate and management scenarios at four sites. The method demonstrated the potential of yield improvement that ranged from 15.8% to 41.5% compared to the current cultivars under mid‐century climate projections. These results highlight the primary role of phenological traits to improve crop adaptation to climate change, as well as traits involved with canopy development and structure. The variability of plant types derived with different models supported model ensembles to handle related uncertainty. Nevertheless, the models agreed in capturing the effect of the heterogeneity in climate conditions across sites on key traits, highlighting the need for context‐specific breeding programmes to improve crop adaptation to climate change. Although further improvement is needed for crop models to fully support breeding programmes, a trait‐based ensemble approach represents a major step towards the integration of crop modelling and breeding to address climate change challenges and develop adaptation options.

Anthropogenic Mixing in Seasonally Stratified Shelf Seas by Offshore Wind Farm Infrastructure - Robert M. Dorrell; Charlie J. Lloyd; Ben J. Lincoln; Tom P. Rippeth; John R. Taylor; Colm-cille P. Caulfield; Jonathan Sharples; Jeff A. Polton; Brian D. Scannell; Deborah M. Greaves; Rob A. Hall; John H. Simpson (Frontiers in Marine Science, 2022)
The offshore wind energy sector has rapidly expanded over the past two decades, providing a renewable energy solution for coastal nations. Sector development has been led in Europe, but is growing globally. Most developments to date have been in well-mixed, i.e., unstratified, shallow-waters near to shore. Sector growth is, for the first time, pushing developments to deep water, into a brand new environment: seasonally stratified shelf seas. Seasonally stratified shelf seas, where water density varies with depth, have a disproportionately key role in primary production, marine ecosystem and biogeochemical cycling. Infrastructure will directly mix stratified shelf seas. The magnitude of this mixing, additional to natural background processes, has yet to be fully quantified. If large enough it may erode shelf sea stratification. Therefore, offshore wind growth may destabilize and fundamentally change shelf sea systems. However, enhanced mixing may also positively impact some marine ecosystems. This paper sets the scene for sector development into this new environment, reviews the potential physical and environmental benefits and impacts of large scale industrialization of seasonally stratified shelf seas and identifies areas where research is required to best utilize, manage, and mitigate environmental change.

Addressing the welfare needs of farmed lumpfish: Knowledge gaps, challenges and solutions - Carlos Garcia de Leaniz; Carolina Gutierrez Rabadan; Sara I. Barrento; Rebecca Stringwell; Paul N. Howes; Ben A. Whittaker; Jessica F. Minett; Robert G. Smith; Craig L. Pooley; Ben J. Overland; Leigh Biddiscombe; Richard Lloyd; et al. (Reviews in Aquaculture, 2022)
Lumpfish ( Cyclopterus lumpus L.) are increasingly being used as cleaner fish to control parasitic sea lice, one of the most important threats to salmon farming. However, lumpfish cannot survive feeding solely on sea lice, and their mortality in salmon net‐pens can be high, which has welfare, ethical and economic implications. The industry is under increasing pressure to improve the welfare of lumpfish, but little guidance exists on how this can be achieved. We undertook a knowledge gap and prioritisation exercise using a Delphi approach with participants from the fish farming sector, animal welfare, academia and regulators to assess consensus on the main challenges and potential solutions for improving lumpfish welfare. Consensus among participants on the utility of 5 behavioural and 12 physical welfare indicators was high (87–89%), reliable (Cronbach's alpha = 0.79, 95CI = 0.69–0.92) and independent of participant background. Participants highlighted fin erosion and body damage as the most useful and practical operational welfare indicators, and blood parameters and behavioural indicators as the least practical. Species profiling revealed profound differences between Atlantic salmon and lumpfish in relation to behaviour, habitat preferences, nutritional needs and response to stress, suggesting that applying a common set of welfare standards to both species cohabiting in salmon net‐pens may not work well for lumpfish. Our study offers 16 practical solutions for improving the welfare of lumpfish and illustrates the merits of the Delphi approach for achieving consensus among stakeholders on welfare needs, targeting research where is most needed and generating workable solutions.

Food security impacts of smallholder farmers’ adoption of dual-purpose sweetpotato varieties in Rwanda - Gideon Danso-Abbeam; Lloyd J. S. Baiyegunhi; Mark D. Laing; Hussein Shimelis (Food Security, 2021)

Bucking the trend of pollinator decline: the population genetics of a range expanding bumblebee - J. V. Huml; J. S. Ellis; K. Lloyd; C. M. Benefer; M. Kiernan; M. J. F. Brown; M. E. Knight (Evolutionary Ecology, 2021)

Independent and combined impact of hypoxia and acute inorganic nitrate ingestion on thermoregulatory responses to the cold - Josh T. Arnold; Stephen J. Bailey; Simon G. Hodder; Naoto Fujii; Alex B. Lloyd (European Journal of Applied Physiology, 2021)
Purpose This study assessed the impact of normobaric hypoxia and acute nitrate ingestion on shivering thermogenesis, cutaneous vascular control, and thermometrics in response to cold stress. Method Eleven male volunteers underwent passive cooling at 10 °C air temperature across four conditions: (1) normoxia with placebo ingestion, (2) hypoxia (0.130 F i O 2 ) with placebo ingestion, (3) normoxia with 13 mmol nitrate ingestion, and (4) hypoxia with nitrate ingestion. Physiological metrics were assessed as a rate of change over 45 min to determine heat loss, and at the point of shivering onset to determine the thermogenic thermoeffector threshold. Result Independently, hypoxia expedited shivering onset time ( p = 0.05) due to a faster cooling rate as opposed to a change in central thermoeffector thresholds. Specifically, compared to normoxia, hypoxia increased skin blood flow ( p = 0.02), leading to an increased core-cooling rate ( p = 0.04) and delta change in rectal temperature ( p = 0.03) over 45 min, yet the same rectal temperature at shivering onset ( p = 0.9). Independently, nitrate ingestion delayed shivering onset time ( p = 0.01), mediated by a change in central thermoeffector thresholds, independent of changes in peripheral heat exchange. Specifically, compared to placebo ingestion, no difference was observed in skin blood flow ( p = 0.5), core-cooling rate ( p = 0.5), or delta change in rectal temperature ( p = 0.7) over 45 min, while nitrate reduced rectal temperature at shivering onset ( p = 0.04). No interaction was observed between hypoxia and nitrate ingestion. Conclusion These data improve our understanding of how hypoxia and nitric oxide modulate cold thermoregulation.

Climate scientists set the bar of proof too high - Elisabeth A. Lloyd; Naomi Oreskes; Sonia I. Seneviratne; Edward J. Larson (Climatic Change, 2021)
Standards of proof for attributing real world events/damage to global warming should be the same as in clinical or environmental lawsuits, argue Lloyd et al. The central question that we raise is effective communication. How can climate scientists best and effectively communicate their findings to crucial non-expert audiences, including public policy makers and civil society? To address this question, we look at the mismatch between what courts require and what climate scientists are setting as a bar of proof. Our first point is that scientists typically demand too much of themselves in terms of evidence, in comparison with the level of evidence required in a legal, regulatory, or public policy context. Our second point is to recommend that the Intergovernmental Panel on Climate Change recommend more prominently the use of the category “more likely than not” as a level of proof in their reports, as this corresponds to the standard of proof most frequently required in civil court rooms. This has also implications for public policy and the public communication of climate evidence.

Species-Specific Variations in the Metabolomic Profiles of Acropora hyacinthus and Acropora millepora Mask Acute Temperature Stress Effects in Adult Coral Colonies - Michael Sweet; Mark Bulling; Dorsa Varshavi; Gavin R. Lloyd; Andris Jankevics; Lukáš Najdekr; Ralf J. M. Weber; Mark R. Viant; Jamie Craggs (Frontiers in Marine Science, 2021)
Coral reefs are suffering unprecedented declines in health state on a global scale. Some have suggested that human assisted evolution or assisted gene flow may now be necessary to effectively restore reefs and pre-condition them for future climate change. An understanding of the key metabolic processes in corals, including under stressed conditions, would greatly facilitate the effective application of such interventions. To date, however, there has been little research on corals at this level, particularly regarding studies of the metabolome of Scleractinian corals. Here, the metabolomic profiles [measured using 1 H nuclear magnetic resonance spectroscopy ( 1 H NMR) and ultra-high-performance liquid chromatography-mass spectrometry (LC-MS)] of two dominant reef building corals, Acropora hyacinthus and A. millepora , from two distinct geographical locations (Australia and Singapore) were characterized. We assessed how an acute temperature stress (an increase of 3.25°C ± 0.28 from ambient control levels over 8 days), shifted the corals’ baseline metabolomic profiles. Regardless of the profiling method utilized, metabolomic signatures of coral colonies were significantly distinct between coral species, a result supporting previous work. However, this strong species-specific metabolomic signature appeared to mask any changes resulting from the acute heat stress. On closer examination, we were able to discriminate between control and temperature stressed groups using a partial least squares discriminant analysis classification model (PLSDA). However, in all cases “late” components needed to be selected (i.e., 7 and 8 instead of 1 and 2), suggesting any treatment effect was small, relative to other sources of variation. This highlights the importance of pre-characterizing the coral colony metabolomes, and of factoring that knowledge into any experimental design that seeks to understand the apparently subtle metabolic effects of acute heat stress on adult corals. Further research is therefore needed to decouple these apparent individual and species-level metabolomic responses to climate change in corals.

The Effects of a Four-Week Neuromuscular Training Program on Landing Kinematics in Pre- and Post-Peak Height Velocity Male Athletes - Paul J. Read; Jon L. Oliver; Ian J. Dobbs; Megan A. Wong; Nakul Tumkur Anil Kumar; Rhodri S. Lloyd (Journal of Science in Sport and Exercise, 2021)

Laboratory and clinical impacts of an overnight laboratory service - Paul R. Ingram; L. Barrett; E. Raby; P. Boan; G. A. Weaire-Buchanan; H. Darragh; P. Lloyd; I. Kay; J. Flexman (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Negative Food Effect of Danirixin: Use of PBPK Modelling to Explore the Effect of Formulation and Meal Type on Clinical PK - Richard S. Lloyd; Martin I. Hingle; Jackie C. Bloomer; Stephen J. Charles; James M. Butler; Alan Paul; Xiaofeng Zhu; Bruce Miller; Donald D’Amico; Alison Donald; Ruth Tal-Singer; Claire Ambery (Pharmaceutical Research, 2020)

Utility of Kinetic and Kinematic Jumping and Landing Variables as Predictors of Injury Risk: A Systematic Review - Jason S. Pedley; Rhodri S. Lloyd; Paul J. Read; Isabel S. Moore; Mark De Ste Croix; Gregory D. Myer; Jon L. Oliver (Journal of Science in Sport and Exercise, 2020)
Purpose Jump-landing assessments provide a means to quantify an individual’s ability to attenuate ground reaction forces, generate lower limb explosive power and maintain joint alignment. In order to identify risk factors that can be targeted through appropriate training interventions, it is necessary to establish which (scalar) objective kinetic, kinematic, and performance measures are most associated with lower-extremity injury. Methods Online searches of MEDLINE, SCOPUS, EBSCOHost, SPORTDiscus and PubMed databases were completed for all articles published before March 2020 in accordance with PRISMA guidelines. Results 40 articles investigating nine jump-landing assessments were included in this review. The 79% of studies using drop jump ( n = 14) observed an association with future injury, while only 8% of countermovement jump studies ( n = 13) observed an association with injury risk. The 57% of studies using unilateral assessments found associations with risk of injury ( n = 14). Studies using performance measures (jump height/distance) as outcome measure were only associated with injury risk in 30% of cases. However, those using kinetic and/or kinematic analyses (knee abduction moment, knee valgus angle, knee separation distance, peak ground reaction force) found associations with injury in 89% of studies. Conclusion The landing element of jump-landing assessments appears to be superior for identifying individuals at greater risk of injury; likely due to a closer representation of the injury mechanism. Consequently, jump-landing assessments that involve attenuation of impact forces such as the drop jump appear most suited for this purpose but should involve assessment of frontal plane knee motion and ground reaction forces.

The Influence of Biological Maturity on Dynamic Force–Time Variables and Vaulting Performance in Young Female Gymnasts - Sylvia Moeskops; Jon L. Oliver; Paul J. Read; John B. Cronin; Gregory D. Myer; G. Gregory Haff; Isabel S. Moore; Rhodri S. Lloyd (Journal of Science in Sport and Exercise, 2020)
Purpose This cross-sectional study investigated dynamic force–time variables and vaulting performance in young female gymnasts of different maturity status. Methods 120 gymnasts aged 5–14 years were sub-divided into maturity groupings using percent of predicted adult height (%PAH) attained. Participants performed three jumping protocols, the squat jump (SJ), countermovement jump (CMJ) and drop jump (DJ), before completing straight jump vaults that were recorded using two-dimensional video. Results Jumping performance improved with biological maturity evidenced by the most mature gymnasts’ producing significantly more absolute force ( P < 0.05; all d > 0.78), impulse ( P < 0.05; all d > 0.75) and power ( P < 0.05; all d > 0.91) than the least mature group, resulting in the greater jump heights ( P < 0.05; all d > 0.70). While, no significant differences were observed in relative peak force across multiple tests, measures of relative peak power did significantly increase with maturity. Based upon regression analyses, maturation was found to influence vertical take-off velocity during vaulting, explaining 41% of the variance in each jumping protocol. Across all tests, the DJ was found to have the highest predictive ability of vaulting vertical take-off velocity, explaining 55% of the total variance. Conclusion Biological maturation impacts jump height and underpinning mechanical variables in young female gymnasts. Vaulting vertical take-off velocity appears to be influenced by maturation and various dynamic force–time variables, particularly those during DJ, which had the highest explained total variance.

Generation of Alkalinity by Stimulation of Microbial Iron Reduction in Acid Rock Drainage Systems: Impact of Natural Organic Matter Types - Martha E. Jimenez-Castaneda; Carolina Scarinci; Adam Burke; Christopher Boothman; David J. Vaughan; Jonathan R. Lloyd; Bart E. van Dongen (Water, Air, & Soil Pollution, 2020)
To determine the role of organic matter in the attenuation of acid rock drainage (ARD), microcosm-based experiments were performed using ARD stimulated with plants and manures. Initial mineralogical, organic geochemical and microbial analyses indicated a predominance of goethite, a substantial amount of organic carbon originating from local sources, and a bacterial community comparable with those detected in a range of ARD sites worldwide. After 100 days of incubation, changes in the mineralogical, organic and microbiological composition of the ARD demonstrated that the plant additions stimulate microbes with the potential to degrade this organic matter but do not necessarily cause substantial Fe(III) reduction. Conversely, the greatest observed stimulation of Fe(III) reduction, associated with an increase in pH to near-neutral values, was observed using manure additions. These results demonstrate that the use of the optimal natural carbon source is important and can promote the metabolism of microorganisms potentially fuelling a range of geomicrobial processes, including iron and sulfate reduction.

Metabolic rate is negatively linked to adult survival but does not explain latitudinal differences in songbirds - Andy J. Boyce; James C. Mouton; Penn Lloyd; Blair O. Wolf; Thomas E. Martin (Ecology Letters, 2020)
Survival rates vary dramatically among species and predictably across latitudes, but causes of this variation are unclear. The rate‐of‐living hypothesis posits that physiological damage from metabolism causes species with faster metabolic rates to exhibit lower survival rates. However, whether increased survival commonly observed in tropical and south temperate latitudes is associated with slower metabolic rate remains unclear. We compared metabolic rates and annual survival rates that we measured across 46 species, and from literature data across 147 species of birds in northern, southern and tropical latitudes. High metabolic rates were associated with lower survival but survival varied substantially among latitudinal regions independent of metabolism. The inability of metabolic rate to explain latitudinal variation in survival suggests (1) species may evolve physiological mechanisms that mitigate physiological damage from cellular metabolism and (2) extrinsic rather than intrinsic sources of mortality are the primary causes of latitudinal differences in survival.

Variation in dissolved organic matter (DOM) stoichiometry in U.K. freshwaters: Assessing the influence of land cover and soil C:N ratio on DOM composition - Christopher A. Yates; Penny J. Johnes; Alun T. Owen; Francesca L. Brailsford; Helen C. Glanville; Christopher D. Evans; Miles R. Marshall; David L. Jones; Charlotte E. M. Lloyd; Tim Jickells; Richard P. Evershed (Limnology and Oceanography, 2019)
Dissolved organic matter (DOM) plays an important role in freshwater biogeochemistry. To investigate the influence of catchment character on the quality and quantity of DOM in freshwaters, 45 sampling sites draining subcatchments of contrasting soil type, hydrology, and land cover within one large upland‐dominated and one large lowland‐dominated catchment were sampled over a 1‐yr period. Dominant land cover in each subcatchment included: arable and horticultural, blanket peatland, coniferous woodland, and improved, unimproved, acid, and calcareous grasslands. The composition of the C, N, and P pool was determined as a function of the inorganic nutrient species (NO 3 − , NO 2 − , NH 4 + , and PO 4 3− ) and dissolved organic nutrient (dissolved organic carbon [DOC], dissolved organic nitrogen [DON], and dissolved organic phosphorus [DOP]) concentrations. DOM quality was assessed by calculation of the molar DOC : DON and DOC : DOP ratios and specific ultraviolet absorbance (SUVA 254 ). In catchments with little anthropogenic nutrient inputs, DON and DOP typically composed > 80% of the total dissolved nitrogen (TDN) and total dissolved phosphorus (TDP) concentrations. By contrast, in heavily impacted agricultural catchments DON and DOP typically comprised 5–15% of TDN and 10–25% of TDP concentrations. Significant differences in DOC : DON and DOC : DOP ratios were observed between land cover class with significant correlations observed between both the DOC : DON and DOC : DOP molar ratios and SUVA 254 ( r s = 0.88 and 0.84, respectively). Analysis also demonstrated a significant correlation between soil C : N ratio and instream DOC : DON/DOP ( r s = 0.79 and 0.71, respectively). We infer from this that soil properties, specifically the C : N ratio of the soil organic matter pool, has a significant influence on the composition of DOM in streams draining through these landscapes.

Corrigendum: A Response to Scientific and Societal Needs for Marine Biological Observations - Nicholas J. Bax; Patricia Miloslavich; Frank Edgar Muller-Karger; Valerie Allain; Ward Appeltans; Sonia Dawn Batten; Lisandro Benedetti-Cecchi; Pier Luigi Buttigieg; Sanae Chiba; Daniel Paul Costa; J. Emmett Duffy; Daniel C. Dunn; et al. (Frontiers in Marine Science, 2019)

Correction to: Mass coral bleaching of P. versipora in Sydney Harbour driven by the 2015–2016 heatwave - Samantha Goyen; Emma F. Camp; Lisa Fujise; Alicia Lloyd; Matthew R. Nitschke; Todd C. LaJeunesse; Tim Kahlke; Peter J. Ralph; David Suggett (Coral Reefs, 2019)

Mass coral bleaching of P. versipora in Sydney Harbour driven by the 2015–2016 heatwave - Samantha Goyen; Emma F. Camp; Lisa Fujise; Alicia Lloyd; Matthew R. Nitschke; Todd LaJeunensse; Tim Kahlke; Peter J. Ralph; David Suggett (Coral Reefs, 2019)

A Response to Scientific and Societal Needs for Marine Biological Observations - Nicholas J. Bax; Patricia Miloslavich; Frank Edgar Muller-Karger; Valerie Allain; Ward Appeltans; Sonia Dawn Batten; Lisandro Benedetti-Cecchi; Pier Luigi Buttigieg; Sanae Chiba; Daniel Paul Costa; J. Emmett Duffy; Daniel C. Dunn; et al. (Frontiers in Marine Science, 2019)

Determinants of Nile perch (Lates niloticus) overfishing and its intensity in Lake Victoria, Tanzania: a double-hurdle model approach - Eliaza Mkuna; Lloyd J. S. Baiyegunhi (Hydrobiologia, 2019)

Effects of Superdispersant-25 on the sorption dynamics of naphthalene and phenanthrene in marine sediments - Luis J. Perez Calderon; Lloyd D. Potts; Alejandro Gallego; James A. Anderson; Ursula Witte (Journal of Soils and Sediments, 2019)

Correction to: The International Mouse Phenotyping Consortium (IMPC): a functional catalogue of the mammalian genome that informs conservation - Violeta Muñoz-Fuentes; Pilar Cacheiro; Terrence F. Meehan; Juan Antonio Aguilar-Pimentel; Arthur L. Beaudet; Steve D. M. Brown; Mary E. Dickinson; Ann M. Flenniken; Paul Flicek; Antonella Galli; Hamed Haseli Mashhadi; Jason D. Heaney; et al. (Conservation Genetics, 2019)

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

Use of a Mutated Protoporphyrinogen Oxidase Gene as an Effective In Vitro Selectable Marker System that Also Conveys in planta Herbicide Resistance in Sugarcane - C. R. van Beek; J. J. Fernhout; J. Kossmann; J. R. Lloyd; C. van der Vyver (Tropical Plant Biology, 2018)

Versatile catechol dioxygenases in Sphingobium scionense WP01T - Muralidharan Muthu; Yakir Ophir; Lucy J. Macdonald; Alankar Vaidya; Gareth Lloyd-Jones (Antonie van Leeuwenhoek, 2018)

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

Predicting athlete ground reaction forces and moments from motion capture - William R. Johnson; Ajmal Mian; Cyril J. Donnelly; David Lloyd; Jacqueline Alderson (Medical & Biological Engineering & Computing, 2018)

Advective pore-water transport of hydrocarbons in North East Scotland coastal sands - Luis J. Perez Calderon; Kathrin Vossen; Lloyd D. Potts; Alejandro Gallego; James A. Anderson; Ursula Witte (Environmental Science and Pollution Research, 2018)

The reproductive ecology of the Antarctic bivalve Aequiyoldia eightsii (Protobranchia: Sareptidae) follows neither Antarctic nor taxonomic patterns - Sally C. Y. Lau; Laura J. Grange; Lloyd S. Peck; Adam J. Reed (Polar Biology, 2018)

Cell division and turgor mediate enhanced plant growth in Arabidopsis plants treated with the bacterial signalling molecule lumichrome - Motlalepula Pholo; Beatrix Coetzee; Hans J. Maree; Philip R. Young; James R. Lloyd; Jens Kossmann; Paul N. Hills (Planta, 2018)

Agronomic evaluation and molecular characterisation of the acetolactate synthase gene in imazapyr tolerant sugarcane (Saccharum hybrid) genotypes - Motselisi J. Koetle; Dyfed Lloyd Evans; Varnika Singh; Sandy J. Snyman; R. Stuart Rutherford; M. Paula Watt (Plant Cell Reports, 2018)

The International Mouse Phenotyping Consortium (IMPC): a functional catalogue of the mammalian genome that informs conservation - Violeta Muñoz-Fuentes; Pilar Cacheiro; Terrence F. Meehan; Juan Antonio Aguilar-Pimentel; Steve D. M. Brown; Ann M. Flenniken; Paul Flicek; Antonella Galli; Hamed Haseli Mashhadi; Martin Hrabě de Angelis; Jong Kyoung Kim; K. C. Kent Lloyd; et al. (Conservation Genetics, 2018)
The International Mouse Phenotyping Consortium (IMPC) is building a catalogue of mammalian gene function by producing and phenotyping a knockout mouse line for every protein-coding gene. To date, the IMPC has generated and characterised 5186 mutant lines. One-third of the lines have been found to be non-viable and over 300 new mouse models of human disease have been identified thus far. While current bioinformatics efforts are focused on translating results to better understand human disease processes, IMPC data also aids understanding genetic function and processes in other species. Here we show, using gorilla genomic data, how genes essential to development in mice can be used to help assess the potentially deleterious impact of gene variants in other species. This type of analyses could be used to select optimal breeders in endangered species to maintain or increase fitness and avoid variants associated to impaired-health phenotypes or loss-of-function mutations in genes of critical importance. We also show, using selected examples from various mammal species, how IMPC data can aid in the identification of candidate genes for studying a condition of interest, deliver information about the mechanisms involved, or support predictions for the function of genes that may play a role in adaptation. With genotyping costs decreasing and the continued improvements of bioinformatics tools, the analyses we demonstrate can be routinely applied.

Use of lumpfish for sea‐lice control in salmon farming: challenges and opportunities - Adam Powell; Jim W. Treasurer; Craig L. Pooley; Alex J. Keay; Richard Lloyd; Albert K. Imsland; Carlos Garcia de Leaniz (Reviews in Aquaculture, 2018)
Efficient sea‐lice control remains one of the most important challenges for the salmon farming industry. The use of wrasse (Labridae) as cleaner fish offers an alternative to medicines for sea‐lice control, but wrasse tend to become inactive in winter. Lumpfish ( Cyclopterus lumpus ) continue to feed on sea‐lice at low temperatures, and commercial production has escalated from thousands of fish in 2010 to well over 30 million juveniles deployed in 2016. However, production still relies on the capture of wild broodstock, which may not be sustainable. To meet global industry needs, lumpfish production needs to increase to reach c. 50 million fish annually and this can only come from aquaculture. We review current production methods and the use of lumpfish in sea cages and identify some of the main challenges and bottlenecks facing lumpfish intensification. Our gap analysis indicates that the areas in most need of research include better control of maturation for year‐round production; formulation of appropriate diets; artificial selection of elite lines with desirable traits; and development of vaccines for certified, disease‐free juvenile production. The welfare of farmed lumpfish also needs to be better quantified, and more information is needed on optimal densities and tank design. Finally, the risk of farmed lumpfish escaping from net pens needs to be critically assessed, and we argue that it might be beneficial to recover cleaner fish from salmon cages after the production cycle, perhaps using them as broodstock, for export to the Asian food markets or for the production of animal feeds.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Bacterial Community Response in Deep Faroe-Shetland Channel Sediments Following Hydrocarbon Entrainment With and Without Dispersant Addition - Luis J. Perez Calderon; Lloyd D. Potts; Evangelia Gontikaki; Cécile Gubry-Rangin; Thomas Cornulier; Alejandro Gallego; James A. Anderson; Ursula Witte (Frontiers in Marine Science, 2018)

Linking muscle metabolism and functional variation to field swimming performance in bluegill sunfish (Lepomis macrochirus) - David J. Ellerby; Shauna Cyr; Angela X. Han; Mika Lin; Lloyd A. Trueblood (Journal of Comparative Physiology B, 2018)

The impacts avoided with a 1.5 °C climate target: a global and regional assessment - Nigel W. Arnell; Jason A. Lowe; Ben Lloyd-Hughes; Timothy J. Osborn (Climatic Change, 2018)

Ethyl Methanesulfonate Mutagenesis and In Vitro Polyethylene Glycol Selection for Drought Tolerance in Sugarcane (Saccharum spp.) - M. Masoabi; J. Lloyd; J. Kossmann; C. van der Vyver (Sugar Tech, 2018)

A case history introducing the oregon ag seminar series - keys to program and research-to-practice success - Marcy J Harrington; Kirk Lloyd (Journal of Agromedicine, 2017)

Medicago truncatula Oleanolic-Derived Saponins Are Correlated with Caterpillar Deterrence - Fanping Cai; Bonnie S. Watson; David Meek; David V. Huhman; Daniel J. Wherritt; Cecile Ben; Laurent Gentzbittel; Brian T. Driscoll; Lloyd W. Sumner; Jacqueline C. Bede (Journal of Chemical Ecology, 2017)

Efficient gene targeting in mouse zygotes mediated by CRISPR/Cas9-protein - Chris J. Jung; Junli Zhang; Elizabeth Trenchard; Kent C. Lloyd; David B. West; Barry Rosen; Pieter J. de Jong (Transgenic Research, 2017)

Parental cooperation in a changing climate: fluctuating environments predict shifts in care division - Orsolya Vincze; András Kosztolányi; Zoltán Barta; Clemens Küpper; Monif Alrashidi; Juan A. Amat; Araceli Argüelles Ticó; Fiona Burns; John Cavitt; Warren C. Conway; Medardo Cruz‐López; Atahualpa Eduardo Desucre‐Medrano; et al. (Global Ecology and Biogeography, 2017)
Aim Parental care improves the survival of offspring and therefore has a major impact on reproductive success. It is increasingly recognized that coordinated biparental care is necessary to ensure the survival of offspring in hostile environments, but little is known about the influence of environmental fluctuations on parental cooperation. Assessing the impacts of environmental stochasticity, however, is essential for understanding how populations will respond to climate change and the associated increasing frequencies of extreme weather events. Here we investigate the influence of environmental stochasticity on biparental incubation in a cosmopolitan ground‐nesting avian genus. Location Global. Methods We assembled data on biparental care in 36 plover populations ( Charadrius spp.) from six continents, collected between 1981 and 2012. Using a space‐for‐time approach we investigate how average temperature, temperature stochasticity (i.e. year‐to‐year variation) and seasonal temperature variation during the breeding season influence parental cooperation during incubation. Results We show that both average ambient temperature and its fluctuations influence parental cooperation during incubation. Male care relative to female care increases with both mean ambient temperature and temperature stochasticity. Local climatic conditions explain within‐species population differences in parental cooperation, probably reflecting phenotypic plasticity of behaviour. Main conclusions The degree of flexibility in parental cooperation is likely to mediate the impacts of climate change on the demography and reproductive behaviour of wild animal populations.

Macruropyxis fulva sp. nov., a new rust (Pucciniales) infecting sugarcane in southern Africa - L. A. Martin; D. Lloyd Evans; L. A. Castlebury; J. T. Sifundza; J. C. Comstock; R. S. Rutherford; S. A. McFarlane (Australasian Plant Pathology, 2017)

Satellite telemetry reveals population specific winter ranges of beluga whales in the Bering Sea - John J. Citta; Pierre Richard; Lloyd F. Lowry; Gregory O'Corry‐Crowe; Marianne Marcoux; Robert Suydam; Lori T. Quakenbush; Roderick C. Hobbs; Denis I. Litovka; Kathryn J. Frost; Tom Gray; Jack Orr; et al. (Marine Mammal Science, 2017)
At least five populations (stocks) of beluga whales ( Delphinapterus leucas ) are thought to winter in the Being Sea, including the Bristol Bay, Eastern Bering Sea (Norton Sound), Anadyr, Eastern Chukchi Sea, and Eastern Beaufort Sea (Mackenzie) populations. Belugas from each population have been tagged with satellite‐linked transmitters, allowing us to describe their winter (January–March) distribution. The objectives of this paper were to determine: (1) If each population winters in the Bering Sea, and if so, where? (2) Do populations return to the same area each year ( i.e ., are wintering areas traditional)? (3) To what extent do the winter ranges of different populations overlap? Tagged belugas from all five populations either remained in, or moved into, the Bering Sea and spent the winter there. Each population wintered in a different part of the Bering Sea and populations with multiple years of data (four of five) returned to the same regions in multiple years. When data were available from two populations that overlapped in the same year, they did not occupy the shared area at the same time. Although our sample sizes were small, the evidence suggests belugas from different populations have traditional winter ranges that are mostly exclusive to each population.

Movements of beluga whales ( Delphinapterus leucas ) in Bristol Bay, Alaska - John J. Citta; Lori T. Quakenbush; Kathryn J. Frost; Lloyd Lowry; Roderick C. Hobbs; Helen Aderman (Marine Mammal Science, 2016)
We describe the annual distribution of beluga whales ( Delphinapterus leucas ) in Bristol Bay, Alaska, using data from 31 satellite‐linked transmitters during 2002–2011. Bristol Bay has one of the largest and best studied Pacific salmon ( Oncorhynchus spp.) fisheries in the world, allowing us to link the seasonal distribution of belugas to that of salmon. During salmon migrations, beluga movements were restricted to river entrances. Belugas generally did not relocate to different river entrances or change bays during peak salmon periods. However, the location of belugas was not related to the number of salmon passing counting towers, suggesting that belugas were either selecting locations that were good for catching salmon or there were simply more salmon than belugas needed to supply their nutritional needs. The distribution of belugas expanded after salmon runs ended, and was greatest in winter when belugas ranged beyond the inner bays, traveling as far west as Cape Constantine. Belugas continued to frequent the inner bays in winter whenever sea ice conditions allowed, e.g ., when winds moved sea ice offshore; however, they were never located south of the southern ice edge in open water or outside of Bristol Bay.

The relationship between hallucinations and FDG-PET in dementia with Lewy bodies - Michael J. Firbank; Jim Lloyd; John T. O’Brien (Brain Imaging and Behavior, 2016)

Improved food quality, quantity and security among Kenyan orphans and vulnerable children: associations with participation in a multisectoral community-based program, age, gender, and sexual risk - Michael L. Goodman; Beatrice J. Selwyn; Robert O. Morgan; Linda E. Lloyd; Moses Mwongera; Stanley Gitari; Philip H. Keiser (Food Security, 2016)

Modelling the influences of climate change-associated sea-level rise and socioeconomic development on future storm surge mortality - Simon J. Lloyd; R. Sari Kovats; Zaid Chalabi; Sally Brown; Robert J. Nicholls (Climatic Change, 2016)

The impacts of climate change across the globe: A multi-sectoral assessment - N. W. Arnell; S. Brown; S. N. Gosling; P. Gottschalk; J. Hinkel; C. Huntingford; B. Lloyd-Hughes; J. A. Lowe; R. J. Nicholls; T. J. Osborn; T. M. Osborne; G. A. Rose; et al. (Climatic Change, 2016)

Global-scale climate impact functions: the relationship between climate forcing and impact - N. W. Arnell; S. Brown; S. N. Gosling; J. Hinkel; C. Huntingford; B. Lloyd-Hughes; J. A. Lowe; T. Osborn; R. J. Nicholls; P. Zelazowski (Climatic Change, 2016)

Predicting Knee Osteoarthritis - Bruce S. Gardiner; Francis G. Woodhouse; Thor F. Besier; Alan J. Grodzinsky; David G. Lloyd; Lihai Zhang; David W. Smith (Annals of Biomedical Engineering, 2016)

Xylem parenchyma cell walls lack a gravitropic response in conifer compression wood - Lloyd A. Donaldson; B. Nanayakkara; K. Radotić; D. Djikanovic-Golubović; A. Mitrović; J. Bogdanović Pristov; J. Simonović Radosavljević; A. Kalauzi (Planta, 2015)

Welfare impacts of smallholder farmers’ participation in maize and pigeonpea markets in Tanzania - Frank E. Mmbando; Edilegnaw Z. Wale; Lloyd J. S. Baiyegunhi (Food Security, 2015)

Erratum to: The chronic effects of an extract of Bacopa monniera (Brahmi) on cognitive function in healthy human subjects - C. Stough; J. Lloyd; J. Clarke; L. A. Downey; C. W. Hutchison; T. Rodgers; P. J. Nathan (Psychopharmacology, 2015)

Lateglacial to Holocene relative sea‐level changes in the Stykkishólmur area, northern Snæfellsnes, Iceland - MARTIN D. BRADER; JEREMY M. LLOYD; MICHAEL J. BENTLEY; ANTHONY J. NEWTON (Journal of Quaternary Science, 2015)
Comparatively little research has been undertaken on relative sea‐level (RSL) change in western Iceland. This paper presents the results of diatom, tephrochronological and radiocarbon analyses on six isolation basins and two coastal lowland sediment cores from the Stykkishólmur area, northern Snæfellsnes, western Iceland. The analyses provide a reconstruction of Lateglacial to mid‐Holocene RSL changes in the region. The marine limit is measured to 65–69 m above sea level (asl), with formation being estimated at 13.5 cal ka BP. RSL fall initially occurred rapidly following marine limit formation, until ca. 12.6 cal ka BP, when the rate of RSL fall decreased. RSL fell below present in the Stykkishólmur area during the early Holocene (by ca. 10 cal ka BP). The rates of RSL change noted in the Stykkishólmur area demonstrate lesser ice thicknesses in Snæfellsnes than Vestfirðir during the Younger Dryas, when viewed in the regional context. Consequently, the data provide an insight into patterns of glacio‐isostatic adjustment surrounding Breiðafjörður, a hypothesized major ice stream at the Last Glacial Maximum.

Rescue of germline transmission from chimeras by IVF after sperm analysis - Ming-Wen Li; Brandon J. Willis; Kristin D. Evans; Renee S. Araiza; Angus Yiu-Fai Lee; K. C. Kent Lloyd (Transgenic Research, 2015)

Pollution, habitat loss, fishing, and climate change as critical threats to penguins - Phil N. Trathan; Pablo García‐Borboroglu; Dee Boersma; Charles‐André Bost; Robert J. M. Crawford; Glenn T. Crossin; Richard J. Cuthbert; Peter Dann; Lloyd Spencer Davis; Santiago De La Puente; Ursula Ellenberg; Heather J. Lynch; et al. (Conservation Biology, 2015)
Cumulative human impacts across the world's oceans are considerable. We therefore examined a single model taxonomic group, the penguins (Spheniscidae), to explore how marine species and communities might be at risk of decline or extinction in the southern hemisphere. We sought to determine the most important threats to penguins and to suggest means to mitigate these threats. Our review has relevance to other taxonomic groups in the southern hemisphere and in northern latitudes, where human impacts are greater. Our review was based on an expert assessment and literature review of all 18 penguin species; 49 scientists contributed to the process. For each penguin species, we considered their range and distribution, population trends, and main anthropogenic threats over the past approximately 250 years. These threats were harvesting adults for oil, skin, and feathers and as bait for crab and rock lobster fisheries; harvesting of eggs; terrestrial habitat degradation; marine pollution; fisheries bycatch and resource competition; environmental variability and climate change; and toxic algal poisoning and disease. Habitat loss, pollution, and fishing, all factors humans can readily mitigate, remain the primary threats for penguin species. Their future resilience to further climate change impacts will almost certainly depend on addressing current threats to existing habitat degradation on land and at sea. We suggest protection of breeding habitat, linked to the designation of appropriately scaled marine reserves, including in the High Seas, will be critical for the future conservation of penguins. However, large‐scale conservation zones are not always practical or politically feasible and other ecosystem‐based management methods that include spatial zoning, bycatch mitigation, and robust harvest control must be developed to maintain marine biodiversity and ensure that ecosystem functioning is maintained across a variety of scales. Contaminación, Pérdida de Hábitat, Pesca y Cambio Climático como Amenazas Críticas para los Pingüinos

Nutritional Effects on the Appearance of Canola and its Attractiveness to the Cabbage Seedpod Weevil - Adam J. Blake; Lloyd M. Dosdall; James A. Tansey (Journal of Insect Behavior, 2014)

Biogeography and conservation of aquatic fauna in spring-fed tropical canyons of the southern Sonoran Desert, Mexico - Michael T. Bogan; Nohemí Noriega-Felix; Sylvette Leonor Vidal-Aguilar; Lloyd T. Findley; David A. Lytle; Oscar G. Gutiérrez-Ruacho; J. Andrés Alvarado-Castro; Alejandro Varela-Romero (Biodiversity and Conservation, 2014)

Endogenously imprinted genes in Drosophila melanogaster - Lori A. McEachern; Nicholas J. Bartlett; Vett K. Lloyd (Molecular Genetics and Genomics, 2014)

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

Experimental influence of pH on the early life-stages of sea urchins II: increasing parental exposure times gives rise to different responses - Coleen C. Suckling; Melody S. Clark; Christine Beveridge; Lars Brunner; Adam D. Hughes; Elizabeth M. Harper; Elizabeth J. Cook; Andrew J. Davies; Lloyd S. Peck (Invertebrate Reproduction & Development, 2014)

The involvement of gibberellin signalling in the effect of soil resistance to root penetration on leaf elongation and tiller number in wheat - Mauricio A. Coelho Filho; Ellen H. Colebrook; David P. A. Lloyd; Colin P. Webster; Sacha J. Mooney; Andrew L. Phillips; Peter Hedden; William R. Whalley (Plant and Soil, 2013)

The impact of culture medium on the development and physiology of biofilms of Pseudomonas fluorescens formed on polyurethane paint - Wendy J. Crookes-Goodson; Caitlin L. Bojanowski; Michelle L. Kay; Pamela F. Lloyd; Andrew Blankemeier; Jennifer M. Hurtubise; Kristi M. Singh; Daniel E. Barlow; Harold D. Ladouceur; D. Matt Eby; Glenn R. Johnson; Peter A. Mirau; et al. (Biofouling, 2013)

Medicago glucosyltransferase UGT72L1: potential roles in proanthocyanidin biosynthesis - Yongzhen Pang; Xiaofei Cheng; David V. Huhman; Junying Ma; Gregory J. Peel; Keiko Yonekura-Sakakibara; Kazuki Saito; Guoan Shen; Lloyd W. Sumner; Yuhong Tang; Jianqi Wen; Jianfei Yun; et al. (Planta, 2013)

Humans, megafauna and environmental change in tropical Australia - MICHAEL I. BIRD; LINDSAY B. HUTLEY; MICHAEL J. LAWES; JON LLOYD; JON G. LULY; PETER V. RIDD; RICHARD G. ROBERTS; SEAN ULM; CHRISTOPHER M. WURSTER (Journal of Quaternary Science, 2013)
Debate concerning the environmental impact of human arrival in Australia has continued for more than a century. Here we review the evidence for human impact and the mechanisms by which humans may have affected the environment of tropical Australia. We limit our review to tropical Australia because, over three decades ago, it was proposed that the imposition of an anthropogenic fire regime upon human occupation of the Australian continent may have resulted in profound changes in regional vegetation and climate across this region. We conclude that ecological processes and vegetation–fire–climate–human feedbacks do exist that could have driven a significant shift in boundary conditions and ecosystem state at the sub‐continental scale through the sustained imposition of an anthropogenic fire regime over tens of millennia. These potential feedbacks operate through the inhibition of forest expansion both directly, by targeted burning at established forest edges and newly irrupted forest patches, and indirectly, through lengthening of the dry season because of changes to the timing of burning. However, the impact of any such anthropogenic forcing may have been entirely overshadowed by the effects of natural climate change and variability, as well as the generally low nutrient status of Australian soils. A robust assessment of the degree to which the environment of tropical Australia at the large scale has been modified from its ‘natural’ state because of human occupation will require new, coordinated collaborations between indigenous traditional landowners, archaeologists, anthropologists, geochronologists, geoscientists, ecologists, climatologists and modellers.

Climate change projections using the IPSL-CM5 Earth System Model: from CMIP3 to CMIP5 - J.-L. Dufresne; M.-A. Foujols; S. Denvil; A. Caubel; O. Marti; O. Aumont; Y. Balkanski; S. Bekki; H. Bellenger; R. Benshila; S. Bony; L. Bopp; et al. (Climate Dynamics, 2013)

Perennial Biomass Grasses and the Mason–Dixon Line: Comparative Productivity across Latitudes in the Southern Great Plains - J. R. Kiniry; L. C. Anderson; M.-V. V. Johnson; K. D. Behrman; M. Brakie; D. Burner; R. L. Cordsiemon; P. A. Fay; F. B. Fritschi; J. H. Houx; C. Hawkes; T. Juenger; et al. (BioEnergy Research, 2013)

Amphetamine and Methamphetamine Have a Direct and Differential Effect on BV2 Microglia Cells - R. A. Shanks; J. R. Anderson; J. R. Taylor; S. A. Lloyd (Bulletin of Experimental Biology and Medicine, 2012)

What controls tropical forest architecture? Testing environmental, structural and floristic drivers - L. Banin; T. R. Feldpausch; O. L. Phillips; T. R. Baker; J. Lloyd; K. Affum‐Baffoe; E. J. M. M. Arets; N. J. Berry; M. Bradford; R. J. W. Brienen; S. Davies; M. Drescher; et al. (Global Ecology and Biogeography, 2012)
Aim To test the extent to which the vertical structure of tropical forests is determined by environment, forest structure or biogeographical history. Location Pan‐tropical. Methods Using height and diameter data from 20,497 trees in 112 non‐contiguous plots, asymptotic maximum height ( H AM ) and height–diameter relationships were computed with nonlinear mixed effects ( NLME ) models to: (1) test for environmental and structural causes of differences among plots, and (2) test if there were continental differences once environment and structure were accounted for; persistence of differences may imply the importance of biogeography for vertical forest structure. NLME analyses for floristic subsets of data (only/excluding Fabaceae and only/excluding Dipterocarpaceae individuals) were used to examine whether family‐level patterns revealed biogeographical explanations of cross‐continental differences. Results H AM and allometry were significantly different amongst continents. H AM was greatest in A sian forests (58.3 ± 7.5 m, 95% CI ), followed by forests in A frica (45.1 ± 2.6 m), A merica (35.8 ± 6.0 m) and A ustralia (35.0 ± 7.4 m), and height–diameter relationships varied similarly; for a given diameter, stems were tallest in A sia, followed by A frica, A merica and A ustralia. Precipitation seasonality, basal area, stem density, solar radiation and wood density each explained some variation in allometry and H AM yet continental differences persisted even after these were accounted for. Analyses using floristic subsets showed that significant continental differences in H AM and allometry persisted in all cases. Main conclusions Tree allometry and maximum height are altered by environmental conditions, forest structure and wood density. Yet, even after accounting for these, tropical forest architecture varies significantly from continent to continent. The greater stature of tropical forests in A sia is not directly determined by the dominance of the family Dipterocarpaceae, as on average non‐dipterocarps are equally tall. We hypothesise that dominant large‐statured families create conditions in which only tall species can compete, thus perpetuating a forest dominated by tall individuals from diverse families.

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)

Previous experiences with humans affect responses of Snares Penguins to experimental disturbance - Ursula Ellenberg; Thomas Mattern; David M. Houston; Lloyd S. Davis; Philip J. Seddon (Journal of Ornithology, 2012)

An introspective glance into damage assessment: challenges and lessons learned from the Paso Robles (San Simeon) earthquake - David McEntire; Jill Souza; Matthew Lloyd Collins; Ekong J. Peters; Abdul-Akeem Sadiq (Natural Hazards, 2012)

Global threats to pinnipeds - Kit M. Kovacs; Alex Aguilar; David Aurioles; Vladimir Burkanov; Claudio Campagna; Nick Gales; Tom Gelatt; Simon D. Goldsworthy; Simon J. Goodman; Greg J. G. Hofmeyr; Tero Härkönen; Lloyd Lowry; et al. (Marine Mammal Science, 2012)

Ocean warming alters species abundance patterns and increases species diversity in an African sub‐tropical reef‐fish community - PENN LLOYD; ÉVA E. PLAGÁNYI; SCARLA J. WEEKS; MARITES MAGNO‐CANTO; GYULA PLAGÁNYI (Fisheries Oceanography, 2012)
The impacts of ocean warming resulting from recent climate change on the abundance patterns of marine species have been well documented in temperate seas of the northern hemisphere, but the impacts of a widening tropical belt are largely unexplored. Using measurements of sea surface temperature and spear‐fishing records for 84 species spanning a 19‐yr period, we examined the effects of ocean warming on a sub‐tropical reef‐fish community on the southeastern coast of Africa. Corresponding with a 0.46°C increase in average sea surface temperature between the time periods 1989–97 and 2002–2007, the ratio of species showing an overall decrease/ no change/increase in abundance was 1 : 3 : 2 among six species at the northern limits of their distribution in the region (temperate species), 1 : 15 : 6 among 22 broadly distributed species, and 1 : 5 : 9 among 15 species at the southern limits of their distribution (tropical species). Also, the relative abundance of temperate species as a whole decreased by 10–13% whereas that of tropical species increased by 9%, and broadly distributed species showed little change. Average species richness and diversity increased 33 and 15% respectively between the two time periods. These results are broadly consistent with a predicted poleward shift in species ranges and a predicted increase in species richness and diversity with increasing sea temperature. Our findings confirm that large‐scale climate change causing a widening of the tropical belt and subsequent ocean warming is having a profound impact on marine species abundance patterns and community composition at a local scale in the sub‐tropics.

Trade-off in ecosystem services of the Somerset Levels and Moors wetlands - M. C. Acreman; R. J. Harding; C. Lloyd; N. P. McNamara; J. O. Mountford; D. J. Mould; B. V. Purse; M. S. Heard; C. J. Stratford; S. J. Dury (Hydrological Sciences Journal, 2011)

Reduction of metastasis using a non-volatile buffer - Arig Ibrahim Hashim; Heather H. Cornnell; Maria de Lourdes Coelho Ribeiro; Dominique Abrahams; Jessica Cunningham; Mark Lloyd; Gary V. Martinez; Robert A. Gatenby; Robert J. Gillies (Clinical & Experimental Metastasis, 2011)

Time–space radiometric normalization of TM/ETM+ images for land cover change detection - Lloyd L. Coulter; Allen S. Hope; Douglas A. Stow; Christopher D. Lippitt; Steven J. Lathrop (International Journal of Remote Sensing, 2011)

QTL alleles for improved fiber quality from a wild Hawaiian cotton, Gossypium tomentosum - Zhengsheng Zhang; Junkang Rong; Vijay N. Waghmare; Peng W. Chee; O. Lloyd May; Robert J. Wright; John R. Gannaway; Andrew H. Paterson (Theoretical and Applied Genetics, 2011)

Mirabilis jalapa mottle virus: a new carlavirus infecting four o’clocks - Gregory J. Hatlestad; Lee Elam; Antonio Gonzalez; Alan M. Lloyd (Archives of Virology, 2011)

Seismic stratigraphy records the deglacial history of Jakobshavn Isbræ, West Greenland - Kelly A. Hogan; Justin K. Dix; Jerry M. Lloyd; Antony J. Long; Carol J. Cotterill (Journal of Quaternary Science, 2011)
Jakobshavn Isbræ is one of the largest ice streams in the Greenland Ice Sheet, presently draining c. 6.5% of the Inland Ice. Here we present high‐resolution Chirp and Sparker sub‐bottom profiles from a seismic survey conducted just outside of the Jakobshavn Isfjord, which provides detailed insight into the glacimarine sedimentary history of the Jakobshavn ice stream during the Holocene. We observe acoustically stratified and homogeneous sediments that drape an irregular substratum and were deposited between ∼10 and c. 7.6k cal a BP. The stratified lower units are interpreted as the product of ice‐proximal glacimarine sedimentation deposited rapidly when the grounded ice margin was located close to depositional basins on topographic highs. The upper acoustically homogenous units reflect suspension settling of fine‐grained material and gravitational flows that were extruded from an increasingly unstable ice margin as the ice retreated into the fjord. Proximity to the ice margin and bedrock topography were the dominant controls on sediment accumulation during deglaciation although the 8.2‐ka cooling event probably influenced the position of the ice margin at the fjord mouth. The post‐glacial sedimentary record is characterized by glacimarine and hemipelagic rainout with an increased ice‐rafted detritus fraction that records sedimentation following ice stream retreat into Jakobshavn Isfjord sometime after c. 7.8k cal a BP. Copyright © 2011 John Wiley & Sons, Ltd.

Quantitative PCR demonstrates a positive correlation between a Rickettsia ‐like organism and severity of strawberry disease lesions in rainbow trout, Oncorhynchus mykiss (Walbaum) - S J Lloyd; S E LaPatra; K R Snekvik; K D Cain; D R Call (Journal of Fish Diseases, 2011)
Strawberry disease (SD) is an inflammatory skin disorder in rainbow trout, Oncorhynchus mykiss (Walbaum). The aetiology of SD is unknown although the 16S rDNA sequence of a Rickettsia ‐like organism (RLO) has been associated with SD lesions using a nested PCR assay. In this study, we developed a Taqman quantitative PCR assay (qPCR) that targeted the RLO 16S rDNA sequence to examine the distribution of RLO relative to lesion status. We compared 18 lesion samples from 13 fish representing high or low lesion severity as judged by gross examination. QPCR results showed that there was a higher number of RLO sequences in high severity lesions (mean of 12 068 copies) compared with fewer copies of RLO sequence in low severity lesions (mean of 3287 copies, P = 0.012). Grossly normal skin samples ( n = 13) from SD‐affected fish were all negative by qPCR except two samples (121 and 139 copies). The qPCR assay described herein is a useful tool to investigate the role of RLO in SD in the absence of a culture system for RLO. Our results demonstrate a positive correlation between copy number and lesion severity consistent with the hypothesis that the RLO is the aetiologic agent of SD.

TRY – a global database of plant traits - J. KATTGE; S. DÍAZ; S. LAVOREL; I. C. PRENTICE; P. LEADLEY; G. BÖNISCH; E. GARNIER; M. WESTOBY; P. B. REICH; I. J. WRIGHT; J. H. C. CORNELISSEN; C. VIOLLE; et al. (Global Change Biology, 2011)
Plant traits – the morphological, anatomical, physiological, biochemical and phenological characteristics of plants and their organs – determine how primary producers respond to environmental factors, affect other trophic levels, influence ecosystem processes and services and provide a link from species richness to ecosystem functional diversity. Trait data thus represent the raw material for a wide range of research from evolutionary biology, community and functional ecology to biogeography. Here we present the global database initiative named TRY, which has united a wide range of the plant trait research community worldwide and gained an unprecedented buy‐in of trait data: so far 93 trait databases have been contributed. The data repository currently contains almost three million trait entries for 69 000 out of the world's 300 000 plant species, with a focus on 52 groups of traits characterizing the vegetative and regeneration stages of the plant life cycle, including growth, dispersal, establishment and persistence. A first data analysis shows that most plant traits are approximately log‐normally distributed, with widely differing ranges of variation across traits. Most trait variation is between species (interspecific), but significant intraspecific variation is also documented, up to 40% of the overall variation. Plant functional types (PFTs), as commonly used in vegetation models, capture a substantial fraction of the observed variation – but for several traits most variation occurs within PFTs, up to 75% of the overall variation. In the context of vegetation models these traits would better be represented by state variables rather than fixed parameter values. The improved availability of plant trait data in the unified global database is expected to support a paradigm shift from species to trait‐based ecology, offer new opportunities for synthetic plant trait research and enable a more realistic and empirically grounded representation of terrestrial vegetation in Earth system models.

Environmental evidence for net methane production and oxidation in putative ANaerobic MEthanotrophic (ANME) archaea - Karen G. Lloyd; Marc J. Alperin; Andreas Teske (Environmental Microbiology, 2011)
Summary Uncultured ANaerobic MEthanotrophic (ANME) archaea are often assumed to be obligate methanotrophs that are incapable of net methanogenesis, and are therefore used as proxies for anaerobic methane oxidation in many environments in spite of uncertainty regarding their metabolic capabilities. Anaerobic methane oxidation regulates methane emissions in marine sediments and appears to occur through a reversal of a methane‐producing metabolism. We tested the assumption that ANME are obligate methanotrophs by detecting and quantifying gene transcription of ANME‐1 across zones of methane oxidation versus methane production in sediments from the White Oak River estuary, North Carolina. ANME‐1 consistently transcribe 16S rRNA and mRNA of methyl coenzyme M reductase ( mcrA ), the key gene for methanogenesis, up to 45 cm into methanogenic sediments. CARD‐FISH shows that ANME‐1 exist as single rod‐shaped cells or pairs of cells. Integrating normalized depth distributions of 16S rDNA and rRNA (measured with qPCR and RT‐qPCR respectively) shows that 26–77% of the rDNA (a proxy for ANME‐1 cell numbers), and 18–76% of the rRNA (a proxy for ANME‐1 activity) occurs within methane‐producing sediments. These results, along with a re‐assessment of the published Iiterature, change the perspective to ANME‐1 as methanogens that are also capable of methane oxidation.

Erratum to: Multi-year observations on the gametogenic ecology of the Antarctic seastar Odontaster validus - Laura J. Grange; Paul A. Tyler; Lloyd S. Peck (Marine Biology, 2011)

Effect of resistance training during hemodialysis on circulating cytokines: a randomized controlled trial - Birinder Singh Bobby Cheema; Haifa Abas; Benjamin C. F. Smith; Anthony J. O’Sullivan; Maria Chan; Aditi Patwardhan; John Kelly; Adrian Gillin; Glen Pang; Brad Lloyd; Klaus Berger; Bernhard T. Baune; et al. (European Journal of Applied Physiology, 2011)

Genetic variants in TLR2 and TLR4 are associated with markers of monocyte activation: the Atherosclerosis Risk in Communities MRI Study - Suzette J. Bielinski; Jennifer L. Hall; James S. Pankow; Eric Boerwinkle; Nena Matijevic-Aleksic; Max He; Lloyd Chambless; Aaron R. Folsom (Human Genetics, 2011)

Does the early frog catch the worm? Disentangling potential drivers of a parasite age–intensity relationship in tadpoles - Thomas R. Raffel; James O. Lloyd-Smith; Stanley K. Sessions; Peter J. Hudson; Jason R. Rohr (Oecologia, 2011)

Meningeal Coccidioidomycosis Diagnosed by Real-Time Polymerase Chain Reaction Analysis of Cerebrospinal Fluid - Matthew J. Binnicker; Alina S. Popa; Jelena Catania; Maria Alexov; Geoffrey Tsaras; Farrell Lloyd; Nancy L. Wengenack; Mark J. Enzler (Mycopathologia, 2011)

The role and regulation of MAFbx/atrogin-1 and MuRF1 in skeletal muscle atrophy - Victoria C. Foletta; Lloyd J. White; Amy E. Larsen; Bertrand Léger; Aaron P. Russell (Pflügers Archiv - European Journal of Physiology, 2011)

Frontally mediated inhibitory processing and white matter microstructure: age and alcoholism effects - Ian M. Colrain; Edith V. Sullivan; Judith M. Ford; Daniel H. Mathalon; Selwyn-Lloyd McPherson; Brian J. Roach; Kate E. Crowley; Adolf Pfefferbaum (Psychopharmacology, 2011)

In vitro culture of the diplomonad fish parasite Spironucleus vortens reveals unusually fast doubling time and atypical biphasic growth - C O M Millet; D Lloyd; C Williams; J Cable (Journal of Fish Diseases, 2011)

Expression of tenascin-C and its isoforms in the breast - David S. Guttery; Jacqueline A. Shaw; Kirsty Lloyd; J. Howard Pringle; Rosemary A. Walker (Cancer and Metastasis Reviews, 2010)

Association of red‐mark syndrome with a Rickettsia ‐like organism and its connection with strawberry disease in the USA - M Metselaar; K D Thompson; R M L Gratacap; M J L Kik; S E LaPatra; S J Lloyd; D R Call; P D Smith; A Adams (Journal of Fish Diseases, 2010)
Red‐mark syndrome (RMS), a disease seen mostly in rainbow trout, Oncorhynchus mykiss , is of unknown aetiology. The research presented here indicates the presence of an intracellular bacterium in RMS‐affected fish. A positive reaction was observed using immunohistochemistry (IHC) with skin lesions, liver, kidney and spleen of affected fish sampled from several locations within the United Kingdom using two different polyclonal antisera raised against Piscirickettsia salmonis . The same reaction was also seen with a number of different anti‐ P. salmonis monoclonal antibodies (MAbs). A disease with similar clinical signs to RMS, referred to as strawberry disease (SD), has been reported in the USA. A Rickettsia ‐like organism (RLO) has recently been associated with SD based on analysis of 16S rDNA sequences. Using the same panel of anti‐ P. salmonis antibodies used to screen the RMS samples, similar staining was obtained in tissue of SD‐affected fish by IHC. A polymerase chain reaction (PCR) using RLO‐specific primers was also performed on RMS‐affected fish from the United Kingdom, and the samples were positive for the RLO 16S rRNA sequence. These findings suggest that the same aetiological agent may be responsible for RMS in the United Kingdom and SD in the USA.

Vision of the body increases interference on the somatic signal detection task - Laura Mirams; Ellen Poliakoff; Richard J. Brown; Donna M. Lloyd (Experimental Brain Research, 2010)

Mitochondrial plasticity in brachiopod (Liothyrella spp.) smooth adductor muscle as a result of season and latitude - Glenn J. Lurman; Till Blaser; Miles Lamare; Lloyd S. Peck; Simon Morley (Marine Biology, 2010)

Leaf nutrient levels and the spatio-temporal distributions of Plutella xylostella and its larval parasitoids Diadegma insulare and Microplitis plutellae in canola - Rana M. Sarfraz; Lloyd M. Dosdall; Adam J. Blake; B. Andrew Keddie (BioControl, 2010)

Biochemical markers for cabbage seedpod weevil (Ceutorhynchus obstrictus (Marsham)) resistance in canola (Brassica napus L.) - Eric J. Shaw; Ron S. Fletcher; Lloyd L. Dosdall; Laima S. Kott (Euphytica, 2009)

Lateglacial to Holocene relative sea‐level changes in the Bjarkarlundur area near Reykhólar, North West Iceland - Jerry M. Lloyd; Hreggviður Norðdahl; Michael J. Bentley; Anthony J. Newton; Owen Tucker; Yongqiang Zong (Journal of Quaternary Science, 2009)
This paper presents results from seven isolation basins to investigate the relative sea‐level history from the Lateglacial and the mid to late Holocene from the Bjarkarlundur area near Reykhólar on the Reykjanes peninsula in North West Iceland. Results presented help to constrain the timing and rate of relative sea‐level (RSL) change since deglaciation and also the timing of deglaciation itself in the Bjarkarlundur area. The marine limit is estimated to be approximately 80 m above sea level based on an isolation basin with sill altitude at 79.1 m. The maximum age of this marine limit and, hence, local deglaciation is estimated at 12.2 14 C ka BP. Relative sea level then fell rapidly during the late Bölling–early Alleröd at a rate of approximately −35 mm 14 C a −1 to below 50 m by 11.4 14 C ka BP. After this the rate of RSL fall decreased significantly during the late Alleröd and Younger Dryas Chronozones (averaging −6 mm 14 C a −1 between 11.4 and 9.7 14 C ka BP). Based on isolation basins with sill altitudes of 51.1 and 41.1 m, our data constrain any possible fluctuation in RSL produced by regrowth of ice during the Younger Dryas to below 10 m. After 9.7 14 C ka BP the rate of RSL fall increased significantly to approximately −23 mm 14 C a −1 to at least 9.0 14 C ka BP. If eustatic sea‐level rise is taken into account and the calibrated timescale is used, actual crustal uplift rates are estimated at +56 and +46 mm cal. a −1 during Lateglacial and early Holocene times, respectively. During the mid to late Holocene RSL then rose to at least 1 m above present‐day levels, gradually falling to the present‐day level from 3.1 14 C ka BP. These results demonstrate the potential of isolation basin data for investigating the timing and rate of RSL change in Iceland. This can add important well‐constrained information on RSL when combined with data from raised beaches. Copyright © 2009 John Wiley & Sons, Ltd.

Does the disturbance hypothesis explain the biomass increase in basin‐wide Amazon forest plot data? - M. GLOOR; O. L. PHILLIPS; J. J. LLOYD; S. L. LEWIS; Y. MALHI; T. R. BAKER; G. LÓPEZ‐GONZALEZ; J. PEACOCK; S. ALMEIDA; A. C. ALVES De OLIVEIRA; E. ALVAREZ; I. AMARAL; et al. (Global Change Biology, 2009)
Positive aboveground biomass trends have been reported from old‐growth forests across the Amazon basin and hypothesized to reflect a large‐scale response to exterior forcing. The result could, however, be an artefact due to a sampling bias induced by the nature of forest growth dynamics. Here, we characterize statistically the disturbance process in Amazon old‐growth forests as recorded in 135 forest plots of the RAINFOR network up to 2006, and other independent research programmes, and explore the consequences of sampling artefacts using a data‐based stochastic simulator. Over the observed range of annual aboveground biomass losses, standard statistical tests show that the distribution of biomass losses through mortality follow an exponential or near‐identical Weibull probability distribution and not a power law as assumed by others. The simulator was parameterized using both an exponential disturbance probability distribution as well as a mixed exponential–power law distribution to account for potential large‐scale blowdown events. In both cases, sampling biases turn out to be too small to explain the gains detected by the extended RAINFOR plot network. This result lends further support to the notion that currently observed biomass gains for intact forests across the Amazon are actually occurring over large scales at the current time, presumably as a response to climate change.

Effects of different technical coordinate system definitions on the three dimensional representation of the glenohumeral joint centre - Amity Cree Campbell; J. A. Alderson; D. G. Lloyd; B. C. Elliott (Medical & Biological Engineering & Computing, 2009)

Contrasting evolution of diversity at two disease-associated chicken genes - Tim Downing; David J. Lynn; Sarah Connell; Andrew T. Lloyd; A. K. Fazlul Haque Bhuiyan; Pradeepa Silva; Arifa N. Naqvi; Rahamame Sanfo; Racine-Samba Sow; Baitsi Podisi; Cliona O’Farrelly; Olivier Hanotte; et al. (Immunogenetics, 2009)

Contrasting evolution of diversity at two disease-associated chicken genes - Tim Downing; David J. Lynn; Sarah Connell; Andrew T. Lloyd; AK Fazlul Haque Bhuiyan; Pradeepa Silva; Arifa N. Naqvi; Rahamame Sanfo; Racine-Samba Sow; Baitsi Podisi; Cliona O’Farrelly; Olivier Hanotte; et al. (Immunogenetics, 2009)

Factors affecting Sciomyzidae (Diptera) across a transect at Skealoghan Turlough (Co. Mayo, Ireland) - Christopher D. Williams; James Moran; Owen Doherty; Rory J. Mc Donnell; Michael J. Gormally; Lloyd V. Knutson; Jean-Claude Vala (Aquatic Ecology, 2009)

Bird community variation across Polylepis woodland fragments and matrix habitats: implications for biodiversity conservation within a high Andean landscape - Huw Lloyd; Stuart J. Marsden (Biodiversity and Conservation, 2008)

Bird migration times, climate change, and changing population sizes - ABRAHAM J. MILLER‐RUSHING; TREVOR L. LLOYD‐EVANS; RICHARD B. PRIMACK; PAUL SATZINGER (Global Change Biology, 2008)
Past studies of bird migration times have shown great variation in migratory responses to climate change. We used 33 years of bird capture data (1970–2002) from Manomet, Massachusetts to examine variation in spring migration times for 32 species of North American passerines. We found that changes in first arrival dates – the unit of observation used in most studies of bird migration times – often differ dramatically from changes in the mean arrival date of the migration cohort as a whole. In our study, the earliest recorded springtime arrival date for each species occurred 0.20 days later each decade. In contrast, the mean arrival dates for birds of each species occurred 0.78 days earlier each decade. The difference in the two trends was largely explained by declining migration cohort sizes, a factor not examined in many previous studies. We found that changes in migration cohort or population sizes may account for a substantial amount of the variation in previously documented changes in migration times. After controlling for changes in migration cohort size, we found that climate variables, migration distance, and date of migration explained portions of the variation in migratory changes over time. In particular, short‐distance migrants appeared to respond to changes in temperature, while mid‐distance migrants responded particularly strongly to changes in the Southern Oscillation Index. The migration times of long‐distance migrants tended not to change over time. Our findings suggest that previously reported changes in migration times may need to be reinterpreted to incorporate changes in migration cohort sizes.

Importance of Molar Ratios in Selenium-Dependent Protection Against Methylmercury Toxicity - Nicholas V. C. Ralston; J. Lloyd Blackwell; Laura J. Raymond (Biological Trace Element Research, 2007)

Multi-year observations on the gametogenic ecology of the Antarctic seastar Odontaster validus - Laura J. Grange; Paul A. Tyler; Lloyd S. Peck (Marine Biology, 2007)

Assessment of δ 13 C and C/N ratios in bulk organic matter as palaeosalinity indicators in Holocene and Lateglacial isolation basin sediments, northwest Scotland - Elizabeth A. V. Mackie; Jeremy M. Lloyd; Melanie J. Leng; Michael J. Bentley; Carol Arrowsmith (Journal of Quaternary Science, 2007)
Carbon isotopes (δ 13 C) and C/N ratios from bulk organic matter have recently been used as alternative proxies for relative sea‐level (RSL) reconstruction where there are problems associated with conventional biological indictors. A previous study on a single isolation basin (Upper Loch nan Eala) in northwest Scotland has shown a clear relationship between δ 13 C, C/N ratios and palaeosalinity from Younger Dryas and Holocene aged sediments. In this paper we present results of δ 13 C and C/N ratio analyses from other isolation basins in northwest Scotland over the Holocene and the Lateglacial period in order to validate this technique. The results from the Holocene sequences support the earlier findings that this technique can be used to identify RSL change from isolation basins over the Holocene in this region. The relationship between δ 13 C, C/N ratios and RSL change is not apparent in sediments of Lateglacial age. Other environmental variables such as atmospheric CO 2 concentration, poor vegetation development and temperature influence δ 13 C values during this period. Copyright © 2007 John Wiley & Sons, Ltd.

Hypoxia tolerance associated with activity reduction is a key adaptation for Laternula elliptica seasonal energetics - Simon A. Morley; Lloyd S. Peck; Andrew J. Miller; Hans O. Pörtner (Oecologia, 2007)

Modification of chicken avian β-defensin-8 at positively selected amino acid sites enhances specific antimicrobial activity - Rowan Higgs; David J. Lynn; Sarah Cahalane; Iñigo Alaña; Chandralal M. Hewage; Tharappel James; Andrew T. Lloyd; Cliona O’Farrelly (Immunogenetics, 2007)

Survival and growth of two heterotrophic hydrothermal vent archaea, Pyrococcus strain GB-D and Thermococcus fumicolans, under low pH and high sulfide concentrations in combination with high temperature and pressure regimes - Virginia P. Edgcomb; Stephen J. Molyneaux; Simone Böer; Carl O. Wirsen; Mak Saito; Michael S. Atkins; Karen Lloyd; Andreas Teske (Extremophiles, 2007)

Fast diffusion along mobile grain boundaries in calcite - Andrew McCaig; Stephen J. Covey-Crump; Walid Ben Ismaïl; Geoffrey E. Lloyd (Contributions to Mineralogy and Petrology, 2006)

Molecular analysis of a sulphate-reducing consortium used to treat metal-containing effluents - C. Boothman; S. Hockin; D. E. Holmes; G. M. Gadd; J. R. Lloyd (BioMetals, 2006)

Comparing patterns of spatial autocorrelation of assemblages of benthic invertebrates in upland rivers in south-eastern Australia - Ralph Mac Nally; Natalie J. Lloyd; P. S. Lake (Hydrobiologia, 2006)

DEVELOPMENT OF DIVING BY HARBOR SEAL PUPS IN TWO REGIONS OF ALASKA: USE OF THE WATER COLUMN - Kathryn J. Frost; Michael A. Simpkins; Robert J. Small; Lloyd F. Lowry (Marine Mammal Science, 2006)
Satellite‐linked dive recorders were attached to 53 harbor seal pups in Prince William Sound (PWS) and at Tugidak Island, Alaska, during 1997–1999. We used generalized additive models and bootstrap techniques to describe pup diving behavior during their first year of life. Pups increased their ability to dive during the first 3–6 mo, as indicated by increases in proportion of time in the water (time wet) and maximum dive depth achieved by a pup each day (max‐depth) values. Time wet and/or max‐depth later decreased, suggesting a seasonal component to diving behavior. Monthly time wet varied from an overall minimum of 0.68 at tagging in July to a maximum of 0.89 in November. Pups spent half of their time wet swimming in water 60–70 m. This strongly suggests they were not feeding on or near bottom during their first year. Average max‐depths and deepest actual dives were similar for PWS and Tugidak pups. PWS pups dove deeper sooner and spent less time wet than Tugidak pups during the first few months after tagging, probably as a result of regional bathymetric differences. Diving behavior and body condition suggest that food availability was not likely a major factor in the population decline in PWS during the period of this study.

Spatial Scale of Autocorrelation of Assemblages of Benthic Invertebrates in Two Upland Rivers in South-Eastern Australia and Its Implications for Biomonitoring and Impact Assessment in Streams - Natalie J Lloyd; Ralph Mac Nally; P. S. Lake (Environmental Monitoring and Assessment, 2006)

“HAIRY CANOLA” – Arabidopsis GL3 Induces a Dense Covering of Trichomes on Brassica napus Seedlings - M. Y. Gruber; S. Wang; S. Ethier; J. Holowachuk; P. C. Bonham-Smith; J. Soroka; A. Lloyd (Plant Molecular Biology, 2006)

The effects of ziprasidone on regional c-Fos expression in the rat forebrain - C. A. Jennings; J. E. Cluderay; J. Gartlon; J. Cilia; A. Lloyd; D. N. C. Jones; E. Southam (Psychopharmacology, 2006)

Genetic mapping and comparative analysis of seven mutants related to seed fiber development in cotton - Junkang Rong; Gary J. Pierce; Vijay N. Waghmare; Carl J. Rogers; Aparna Desai; Peng W. Chee; O. Lloyd May; John R. Gannaway; Jonathan F. Wendel; Thea A. Wilkins; Andrew H. Paterson (Theoretical and Applied Genetics, 2005)

Evidence and Implications of Recent Climate Change in Northern Alaska and Other Arctic Regions - Larry D. Hinzman; Neil D. Bettez; W. Robert Bolton; F. Stuart Chapin; Mark B. Dyurgerov; Chris L. Fastie; Brad Griffith; Robert D. Hollister; Allen Hope; Henry P. Huntington; Anne M. Jensen; Gensuo J. Jia; et al. (Climatic Change, 2005)

DIFFERENTIAL MOVEMENTS BY HARBOR SEAL PUPS IN CONTRASTING ALASKA ENVIRONMENTS - Robert J. Small; Lloyd F. Lowry; Jay M. Hoef; Kathryn J. Frost; Robert A. Delong; Michael J. Rehberg (Marine Mammal Science, 2005)

Mapping and characterization of new EST-derived microsatellites for potato (Solanum tuberosum L.) - S. Feingold; J. Lloyd; N. Norero; M. Bonierbale; J. Lorenzen (Theoretical and Applied Genetics, 2005)

Dissolution characteristics of central Florida phosphate rock in an acidic sandy soil - Z. L. He; H. Yao; D. V. Calvert; P. J. Stoffella; X. E. Yang; G. Chen; G. M. Lloyd (Plant and Soil, 2005)

Bulk organic δ 13 C and C/N ratios as palaeosalinity indicators within a Scottish isolation basin - Elizabeth A. V. Mackie; Melanie J. Leng; Jeremy M. Lloyd; Carol Arrowsmith (Journal of Quaternary Science, 2005)
Microfossils in isolation basin sediments are frequently used to reconstruct sea‐level change, but preservation problems and non‐analogue situations can limit their usefulness. Here we investigate the potential of stable carbon isotopes (δ 13 C) and C/N ratios from bulk organic matter, as an alternative proxy of salinity within isolation basin sediments from a basin in northwest Scotland. Within the Holocene sediment δ 13 C and C/N are determined largely by the mean weighted values of the predominant source of the organic material. Analysis of modern materials and comparison with the diatom record shows that the marine parts of the sequence are dominated by high δ 13 C and variable C/N. In the fresh water sequences the organic material is a mixture of both freshwater aquatic and terrestrial plant input that have relatively low δ 13 C and high C/N. The application of δ 13 C and C/N ratios in the studied basin in general follow the environmental change recorded by the diatoms and shows the potential of bulk organic matter in the investigation of salinity change in isolation basins. Copyright © 2005 John Wiley & Sons, Ltd.

The synthetic form of a novel chicken ?-defensin identified in silico is predominantly active against intestinal pathogens - Rowan Higgs; David J. Lynn; Susan Gaines; Jessica McMahon; Joanna Tierney; Tharappel James; Andrew T. Lloyd; Grace Mulcahy; Cliona O?Farrelly (Immunogenetics, 2005)

The nature of spatial transitions in the Arctic - H. E. Epstein; J. Beringer; W. A. Gould; A. H. Lloyd; C. D. Thompson; F. S. Chapin; G. J. Michaelson; C. L. Ping; T. S. Rupp; D. A. Walker (Journal of Biogeography, 2004)
Aim Describe the spatial and temporal properties of transitions in the Arctic and develop a conceptual understanding of the nature of these spatial transitions in the face of directional environmental change. Location Arctic tundra ecosystems of the North Slope of Alaska and the tundra‐forest region of the Seward Peninsula, Alaska Methods We synthesize information from numerous studies on tundra and treeline ecosystems in an effort to document the spatial changes that occur across four arctic transitions. These transitions are: (i) the transition between High‐Arctic and Low‐Arctic systems, (ii) the transition between moist non‐acidic tundra (MNT) and moist acidic tundra (MAT, also referred to as tussock tundra), (iii) the transition between tussock tundra and shrub tundra, (iv) the transition between tundra and forested systems. By documenting the nature of these spatial transitions, in terms of their environmental controls and vegetation patterns, we develop a conceptual model of temporal dynamics of arctic ecotones in response to environmental change. Results Our observations suggest that each transition is sensitive to a unique combination of controlling factors. The transition between High and Low Arctic is sensitive primarily to climate, whereas the MNT/MAT transition is also controlled by soil parent material, permafrost and hydrology. The tussock/shrub tundra transition appears to be responsive to several factors, including climate, topography and hydrology. Finally, the tundra/forest boundary responds primarily to climate and to climatically associated changes in permafrost. There were also important differences in the demography and distribution of the dominant plant species across the four vegetation transitions. The shrubs that characterize the tussock/shrub transition can achieve dominance potentially within a decade, whereas spruce trees often require several decades to centuries to achieve dominance within tundra, and Sphagnum moss colonization of non‐acidic sites at the MNT/MAT boundary may require centuries to millennia of soil development. Main conclusions We suggest that vegetation will respond most rapidly to climatic change when (i) the vegetation transition correlates more strongly with climate than with other environmental variables, (ii) dominant species exhibit gradual changes in abundance across spatial transitions, and/or (iii) the dominant species have demographic properties that allow rapid increases in abundance following climatic shifts. All three of these properties characterize the transition between tussock tundra and low shrub tundra. It is therefore not surprising that of the four transitions studied this is the one that appears to be responding most rapidly to climatic warming.

Specificity and functional impact of post-exercise depression of cortically evoked motor potentials in man - A. T. Humphry; E. J. Lloyd-Davies; R. J. Teare; K. E. Williams; P. H. Strutton; N. J. Davey (European Journal of Applied Physiology, 2004)

Bioinformatic discovery and initial characterisation of nine novel antimicrobial peptide genes in the chicken - David J. Lynn; Rowan Higgs; Susan Gaines; Joanna Tierney; Tharappel James; Andrew T. Lloyd; Mario A. Fares; Grace Mulcahy; Cliona O’Farrelly (Immunogenetics, 2004)

A taxonomic revision of Parahebe (Plantaginaceae) in New Zealand - P. J. Garnock‐Jones; D. G. Lloyd (New Zealand Journal of Botany, 2004)
Seventeen species of Parahebe are recognised for New Zealand, an increase of six from the most recent Flora treatment. The new species result from division of P. catarractae sens. lat. into P. catarractae (now confined to Fiordland), P. martinii (Marlborough), and P . lanceolata (North Island and North‐West Nelson); two new species ( P. senex in North‐West Nelson and P. spectabilis in the Takitimu Range); and acceptance of P. brevistylis and P. laxa at species rank. We also describe two subspecies in P. cheesemanii: subsp. cheesemanii from Nelson and subsp. flabellata from Arthur's Pass. Species limits are discussed in terms of morphological and flavonoid evidence, and some limited data on natural and artificial hybrids are also presented. Problems of the generic limits in the Veroniceae are discussed in relation to Parahebe. Parahebe appears to be paraphyletic and future changes in nomenclature are likely. This treatment covers the New Zealand plants treated as Parahebe in recent Floras.

The generic position of Austrofestuca littoralis and the reinstatement of Hookerochloa and Festucella (Poaceae) based on evidence from nuclear (ITS) and chloroplast ( trn L ‐trn F) DNA sequences - A. M. Hunter; D. A. Orlovich; K. M. Lloyd; W. G. Lee; D. J. Murphy (New Zealand Journal of Botany, 2004)
The segregation of the grass genus Austrofestuca from Festuca has been debated because in some respects Austrofestuca is morphologically similar to Poa. Analyses of DNA sequence information from nuclear (internal transcribed spacer) and chloroplast ( trn L ‐trn F) genomes indicate that Austrofestuca is not monophyletic. Austrofestuca littoralis is closely related to Poa, while A. eriopoda and A. hookeriana are placed in a clade containing Arctagrostis, Dupontia, and Arctophila. Whilst Austrofestuca littoralis is nested within the Poa clade, our data do not exclude the possibility that A. littoralis is sister to Poa. A range of morphological characters supports the differentiation of A. eriopoda and A. hookeriana from A. littoralis. We reinstate the genera Festucella and Hookerochloa to accommodate A. eriopoda and A. hookeriana, respectively.

Variation in wood density determines spatial patterns inAmazonian forest biomass - Timothy R. Baker; Oliver L. Phillips; Yadvinder Malhi; Samuel Almeida; Luzmila Arroyo; Anthony Di Fiore; Terry Erwin; Timothy J. Killeen; Susan G. Laurance; William F. Laurance; Simon L. Lewis; Jon Lloyd; et al. (Global Change Biology, 2004)
Uncertainty in biomass estimates is one of the greatest limitations to models of carbon flux in tropical forests. Previous comparisons of field‐based estimates of the aboveground biomass (AGB) of trees greater than 10 cm diameter within Amazonia have been limited by the paucity of data for western Amazon forests, and the use of site‐specific methods to estimate biomass from inventory data. In addition, the role of regional variation in stand‐level wood specific gravity has not previously been considered. Using data from 56 mature forest plots across Amazonia, we consider the relative roles of species composition (wood specific gravity) and forest structure (basal area) in determining variation in AGB. Mean stand‐level wood specific gravity, on a per stem basis, is 15.8% higher in forests in central and eastern, compared with northwestern Amazonia. This pattern is due to the higher diversity and abundance of taxa with high specific gravity values in central and eastern Amazonia, and the greater diversity and abundance of taxa with low specific gravity values in western Amazonia. For two estimates of AGB derived using different allometric equations, basal area explains 51.7% and 63.4%, and stand‐level specific gravity 45.4% and 29.7%, of the total variation in AGB. The variation in specific gravity is important because it determines the regional scale, spatial pattern of AGB. When weighting by specific gravity is included, central and eastern Amazon forests have significantly higher AGB than stands in northwest or southwest Amazonia. The regional‐scale pattern of species composition therefore defines a broad gradient of AGB across Amazonia.

The above‐ground coarse wood productivity of 104 Neotropical forest plots - Yadvinder Malhi; Timothy R. Baker; Oliver L. Phillips; Samuel Almeida; Esteban Alvarez; Luzmilla Arroyo; Jerome Chave; Claudia I. Czimczik; Anthony Di Fiore; Niro Higuchi; Timothy J. Killeen; Susan G. Laurance; et al. (Global Change Biology, 2004)
The net primary production of tropical forests and its partitioning between long‐lived carbon pools (wood) and shorter‐lived pools (leaves, fine roots) are of considerable importance in the global carbon cycle. However, these terms have only been studied at a handful of field sites, and with no consistent calculation methodology. Here we calculate above‐ground coarse wood carbon productivity for 104 forest plots in lowland New World humid tropical forests, using a consistent calculation methodology that incorporates corrections for spatial variations in tree‐size distributions and wood density, and for census interval length. Mean wood density is found to be lower in more productive forests. We estimate that above‐ground coarse wood productivity varies by more than a factor of three (between 1.5 and 5.5 Mg C ha −1 a −1 ) across the Neotropical plots, with a mean value of 3.1 Mg C ha −1 a −1 . There appear to be no obvious relationships between wood productivity and rainfall, dry season length or sunshine, but there is some hint of increased productivity at lower temperatures. There is, however, also strong evidence for a positive relationship between wood productivity and soil fertility. Fertile soils tend to become more common towards the Andes and at slightly higher than average elevations, so the apparent temperature/productivity relationship is probably not a direct one. Coarse wood productivity accounts for only a fraction of overall tropical forest net primary productivity, but the available data indicate that it is approximately proportional to total above‐ground productivity. We speculate that the large variation in wood productivity is unlikely to directly imply an equivalent variation in gross primary production. Instead a shifting balance in carbon allocation between respiration, wood carbon and fine root production seems the more likely explanation.

Soil carbon inventories and δ 13 C along a moisture gradient in Botswana - M. I. Bird; E. M. Veenendaal; J. J. Lloyd (Global Change Biology, 2004)
We present a study of soil organic carbon (SOC) inventories and δ 13 C values for 625 soil cores collected from well‐drained, coarse‐textured soils in eight areas along a 1000 km moisture gradient from Southern Botswana, north into southern Zambia. The spatial distribution of trees and grass in the desert, savannah and woodland ecosystems along the transect control large systematic local variations in both SOC inventories and δ 13 C values. A stratified sampling approach was used to smooth this variability and obtain robust weighted‐mean estimates for both parameters. Weighted SOC inventories in the 0–5 cm interval of the soils range from 7 mg cm −2 in the driest area (mean annual precipitation, MAP=225 mm) to 41±12 mg cm −2 in the wettest area (MAP=910 mm). For the 0–30 cm interval, the inventories are 37.8 mg cm −2 for the driest region and 157±33 mg cm −2 for the wettest region. SOC inventories at intermediate sites increase as MAP increases to approximately 400–500 mm, but remain approximately constant thereafter. This plateau may be the result of feedbacks between MAP, fuel load and fire frequency. Weighted δ 13 C values decrease linearly in both the 0–5 and 0–30 cm depth intervals as MAP increases. A value of –17.5±1.0‰ characterizes the driest areas, while a value of −25±0.7‰ characterizes the wettest area. The decrease in δ 13 C value with increasing MAP reflects an increasing dominance of C 3 vegetation as MAP increases. SOC in the deeper soil (5–30 cm depth) is, on average, 0.4±0.3‰ enriched in 13 C relative to SOC in the 0–5 cm interval.

Rhizoctonia crown and root rot of the pasture legume, sulla (Hedysarum coronarium) - M. J. Ryley; D. L. Lloyd; B. Johnson; K. C. Teasdale; J. M. Mackie (Australasian Plant Pathology, 2004)

Selective Dequenching by Photobleaching Increases Fluorescence Probe Visibility - K. E. Roberts; A. K. O'Keeffe; C. J. Lloyd; D. J. Clarke (Journal of Fluorescence, 2003)

Correlates of geographic range size in New Zealand Chionochloa (Poaceae) species - Kelvin M. Lloyd; J. Bastow Wilson; William G. Lee (Journal of Biogeography, 2003)
Aim To test for correlations between plant traits and geographic range size. Location: New Zealand. Methods Trait data were derived from comparative experiments, in which plants were grown in pots or in a common garden, that tested for intrinsic differences among the species in traits relating to growth, reproduction and dispersal. Controlled experiments were used to test for differences in responses to drought and waterlogging stress. Geographic range size was measured as the number of 10 km grid squares in the New Zealand region containing at least one occurrence of the species. Results Growth rate, dispersal capacity and environmental tolerance were all positively related to geographic range size. Geographically restricted species tended to have more variable flowering between years. Flowering intensity, reproductive allocation, seed set, diaspore size, and responses to single environmental factors were not related to geographic range size. Main conclusions The differences between range‐restricted and widespread Chionochloa species appear to represent alternative strategies of coping with environmental change in a dynamic landscape. Range‐restricted species are specialized to temporally persistent habitats that are of limited geographic extent. As a consequence, they have evolved traits that conflict with persistence in widespread habitats. The implication for conservation management is that the conservation of rare plants will frequently depend on protection of their habitats. The widespread Chionochloa species possess traits that enable them to disperse to and occupy a greater range of habitats. These traits have allowed some of these species to expand their ranges following environmental changes that favoured an increase in grassland extent.

Vergence-mediated changes in the axis of eye rotation during the human vestibulo-ocular reflex can occur independent of eye position - Americo A. Migliaccio; Phillip D. Cremer; Swee T. Aw; G. Michael Halmagyi; Ian S. Curthoys; Lloyd B. Minor; Michael J. Todd (Experimental Brain Research, 2003)

Male-biased sex ratios in New Zealand fur seal pups relative to environmental variation - Corey J. A. Bradshaw; Robert G. Harcourt; Lloyd S. Davis (Behavioral Ecology and Sociobiology, 2003)

Competitive Abilities of Rare and Common Plants: Comparisons Using Acaena (Rosaceae) and Chionochloa (Poaceae) from New Zealand - Kelvin M. Lloyd; William G. Lee; J. Bastow Wilson (Conservation Biology, 2002)
It is commonly suggested that rare plant species are poor competitors. However, the study of rarity and competitive ability has, like much of the research on rare species, been hindered by insufficient sample size, scarce use of experimental methods, and lack of comparison with common species. We used a within‐taxon comparative approach to test for differences in competitive ability between rare and common species in two genera, Acaena ( Rosaceae: six rare and four common species) and Chionochloa ( Poaceae: four rare and five common species). We grew plants in replicated experiments at two levels of soil fertility and with two levels of competition, in monoculture or mixed with the introduced grass Agrostis capillaris . Competitive response was measured as relative yield, relative tiller increase, and change in live‐leaf fraction. Rarity was measured by geographic range size, defined as the number of 10‐km grid squares occupied by each species in New Zealand. The relationship between competitive ability and geographic range size was tested with correlations. Within Acaena , four of the rare species had high competitive ability, but there was no general relationship between competitive ability and rarity at either high or low levels of fertility. Differences in competitive ability appeared related to differences in ecological distribution rather than to rarity or commonness in a geographic sense. Within Chionochloa , common species tended to be stronger competitors than rare species, with the relationship being significant at the low level of fertility. Several of the common Chionochloa species have expanded their geographic ranges relatively recently, consistent with their greater competitive ability. Conversely, rare Chionochloa species occupy specialized habitats that may be interpreted as refuges from competition. Disparate results from Acaena and Chionochloa do not support the notion that rare species are generally poor competitors. Although rare species may have low competitive ability in some cases, it should not be assumed to be a cause of rarity for all rare species.

Evaluation of the AERx Pulmonary Delivery System for Systemic Delivery of a Poorly Soluble Selective D-1 Agonist, ABT-431 - Franklin W. Okumu; Rai-Yun Lee; James D. Blanchard; Anthony Queirolo; Christine M. Woods; Peter M. Lloyd; Jerry Okikawa; Igor Gonda; Stephen J. Farr; Reid Rubsamen; Akwete L. Adjei; Richard J. Bertz (Pharmaceutical Research, 2002)

Contemporary and fossil foraminifera from isolation basins in northwest Scotland - J. M. Lloyd; J. R. Evans (Journal of Quaternary Science, 2002)
Isolation basins are widely used in sea‐level reconstructions, but contemporary analogues have been poorly studied comparatively. Recent research has identified isolation basins with extended transitional isolation contacts that pose problems in sea‐level interpretations. This paper presents foraminiferal results from 24 contemporary isolation basins combined with data from two isolation basins with extended isolation contacts. Foraminiferal associations identified from the contemporary basins show a clear relationship with water salinity and sill altitude that supports interpretation of the extended fossil sequences. An association dominated by Miliammina fusca , Mf, signifies a basin close to final isolation from marine influence. Increasing marine inundation of basins is signified by a series of associations dominated by the following foraminifera; Ja, Jadammina macrescens and M. fusca ; ME, M. fusca and Elphidium williamsoni ; Ew, E. williamsoni ; HE, Haynesina germanica and E. williamsoni ; Nd, Nonion depressulus . These associations can be used to interpret the sedimentary isolation sequences from Loch nan Corr and Rumach VI. A pilot study of the stable isotope signature from the two species H. germanica and E. williamsoni is reported from Rumach VI and Loch nan Corr. The results show the potential of stable isotope analysis for environmental reconstruction from isolation basins, in particular using δ 18 O for salinity reconstruction. Copyright © 2002 John Wiley & Sons, Ltd.

Mexican native trouts: a review of their history and current systematic and conservation status - Dean A. Hendrickson; Héctor Espinosa Pérez; Lloyd T. Findley; William Forbes; Joseph R. Tomelleri; Richard L. Mayden; Jennifer L. Nielsen; Buddy Jensen; Gorgonio Ruiz Campos; Alejandro Varela Romero; Albert van der Heiden; Faustino Camarena; et al. (Reviews in Fish Biology and Fisheries, 2002)

Differential experimental micrometastasis to lung, liver, and bone with lacZ-tagged CWR22R prostate carcinoma cells - Julianne L. Holleran; Carson J. Miller; Nancy L. Edgehouse; Theresa P. Pretlow; Lloyd A. Culp (Clinical & Experimental Metastasis, 2002)

MOVEMENTS OF SATELLITE‐TAGGED SUBADULT AND ADULT HARBOR SEALS IN PRINCE WILLIAM SOUND, ALASKA - Lloyd F. Lowry; Kathryn J. Frost; Jay M. Ver Hoep; Robert A. Delong (Marine Mammal Science, 2001)
A bstract Satellite‐linked tags were attached to 49 subadult and adult harbor seals captured in Prince William Sound (PWS), Alaska, and their movements were monitored during 1992–1997. Seals were tracked for a total of 5,517 seal‐days and were located on about 80% of the days that tags transmitted. Most locations were in or near PWS, but some juvenile seals moved 300–500 km east and west into the Gulf of Alaska. While several seals travelled to 50–100 km offshore, virtually all locations were in water 2 to >1,500 km 2 , and were smallest during June‐July. Mean haul‐out to at‐sea distance was 5–10 km for adults and generally 10–25 km for juveniles. Satellite‐linked tags provided an effective means of monitoring and describing the full range of harbor seal movements in this region, with the exception of late summer when tags were shed during the molt.

DIVING BEHAVIOR OF SUBADULT AND ADULT HARBOR SEALS IN PRINCE WILLIAM SOUND, ALASKA - Kathryn J. Frost; Michael A. Simpkins; Lloyd F. Lowry (Marine Mammal Science, 2001)
A bstract Satellite‐linked depth recorders (SDRs) were attached to 47 harbor seals in Prince William Sound, Alaska, during 1992–1996. Parameters describing diving effort, diving focus, and focal depth (depth bin to which diving was focused) were calculated from binned data on maximum dive depth and time spent at depth, and analyzed using repeated‐measures mixed models. This analysis method accounted for individual variability, temporal autocorrelation, and the binned nature of SDR data, which are often ignored using standard statistical techniques. Results indicated that diving effort remained steady from September to April, when seals spent 68%‐75% of their overall time in the water. Time spent in the water declined to 60% in May and to about 40% in July. Seals spent the most time in the water at night and the least in the morning. The diving of all seals in all months was highly focused. Overall, diving was focused to one depth bin approximately 75% of the time. Diving was more focused for females than for males and subadults. Focal dive depth was deepest in winter and shallowest during May‐July. Focal depth and diving focus varied by region. Collinearity between month and region in the focal depth model suggests that seals move in winter to regions where prey are found deeper in the water column. Variations in diving behavior presumably result from combinations of regional bathymetry, seasonal cycles in type or depth distribution of prey, and seal life‐cycle events such as reproduction and molting.

Seasonal variations of net CO 2 exchange in European Arctic ecosystems - T. Laurila; H. Soegaard; C. R. Lloyd; M. Aurela; J.-P. Tuovinen; C. Nordstroem (Theoretical and Applied Climatology, 2001)

Surface fluxes of heat and water vapour from sites in the European Arctic - C. R. Lloyd; R. J. Harding; T. Friborg; M. Aurela (Theoretical and Applied Climatology, 2001)

Progress in understanding of land surface/atmosphere exchanges at high latitudes - R. J. Harding; S.-E. Gryning; S. Halldin; C. R. Lloyd (Theoretical and Applied Climatology, 2001)

The chronic effects of an extract of Bacopa monniera (Brahmi) on cognitive function in healthy human subjects - Stough C.; Nathan P.; Lloyd J.; Clarke J.; Hutchison C.; Downey L.; Rodgers T. (Psychopharmacology, 2001)

Geographical patterns of genetic variation in two species of Stylosanthes Sw. using amplified fragment length polymorphism - M. C. Sawkins; B. L. Maass; B. C. Pengelly; H. J. Newbury; B. V. Ford‐Lloyd; N. Maxted; R. Smith (Molecular Ecology, 2001)
Understanding the extent and distribution of genetic diversity within a species is essential for the development of effective conservation strategies. The objective of this study was to assess genetic variation using amplified fragment length polymorphisms (AFLP) in two species of the tropical legume genus Stylosanthes Sw. Annual, S. humilis (2 n = 20) and perennial, S. viscosa (2 n = 20) are found throughout tropical America, and are sympatric for much of their range of distribution. One hundred and eleven accessions, covering a wide geographical range, were selected for AFLP analysis. Binary data matrices derived from DNA banding patterns were analysed using the software programs ntsys‐pc and arlequin . Several accessions were found to be misidentified. Of the S. humilis accessions, the overall average similarity value was (0.72) slightly higher than the value obtained for S. viscosa (0.67). Cluster analysis and principal coordinate analysis grouped accessions from both species by geographical origin, with a few exceptions. Analysis of molecular variance ( amova ) in S. humilis revealed 59.4% of the variation among groups formed from the cluster analysis. This was highly significant ( P S. viscosa amova also revealed more variation among than within groups (66.5%). This was also highly significant ( P ex situ are of Brazilian and Venezuelan origin. This study has identified areas in Central America and Mexico for which novel genetic variation may be found and where conservation activities should be focused.

Positive interactions under nurse-plants: spatial scale, stress gradients and benefactor size - Joshua J. Tewksbury; John D. Lloyd (Oecologia, 2001)

Essential genes in proximal 3L heterochromatin of Drosophila melanogaster - S. Schulze; D. A. R. Sinclair; E. Silva; K. A. Fitzpatrick; M. Singh; V. K. Lloyd; K. A. Morin; J. Kim; D. G. Holm; J. A. Kennison; B. M. Honda (Molecular Genetics and Genomics, 2001)

Effectiveness of different classes of molecular marker for classifying and revealing variation in rice (Oryza sativa) germplasm - P.S. Virk; J. Zhu; H.J. Newbury; G.J. Bryan; M.T. Jackson; B.V. Ford-Lloyd (Euphytica, 2000)

Are mapped markers more useful for assessing genetic diversity? - P. S. Virk; H. J. Newbury; M. T. Jackson; B. V. Ford-Lloyd (Theoretical and Applied Genetics, 2000)

Turbulence Statistics Above And Within Two Amazon Rain Forest Canopies - B. Kruijt; Y. Malhi; J. Lloyd; A. D. Norbre; A. C. Miranda; M. G. P. Pereira; A. Culf; J. Grace (Boundary-Layer Meteorology, 2000)

Structural adaptation rather than water conservation was observed in Scots pine over a range of wet to dry climates - S. Palmroth; F. Berninger; E. Nikinmaa; J. Lloyd; P. Pulkkinen; P. Hari (Oecologia, 1999)

Centimeter-Level Positioning of a U. S. Coast Guard Buoy Tender - David B. Zilkoski; J. Don D'Onofrio; Rudolf J. Fury; Curtis L. Smith; Lloyd C. Huff; Barry J. Gallagher (GPS Solutions, 1999)

Hydrogen peroxide is a product of oxygen consumption byTrichomonas vaginalis - Alan Chapman; David J. Linstead; David Lloyd (Journal of Biosciences, 1999)

Productivity of forests in the Eurosiberian boreal region and their potential to act as a carbon sink –‐ a synthesis - E. ‐D. Schulze; J. Lloyd; F. M. Kelliher; C. Wirth; C. Rebmann; B. Lühker; M. Mund; A. Knohl; I. M. Milyukova; W. Schulze; W. Ziegler; A. β. Varlagin; et al. (Global Change Biology, 1999)
Summary Based on review and original data, this synthesis investigates carbon pools and fluxes of Siberian and European forests (600 and 300 million ha, respectively). We examine the productivity of ecosystems, expressed as positive rate when the amount of carbon in the ecosystem increases, while (following micrometeorological convention) downward fluxes from the atmosphere to the vegetation (NEE = Net Ecosystem Exchange) are expressed as negative numbers. Productivity parameters are Net Primary Productivity (NPP=whole plant growth), Net Ecosystem Productivity (NEP = CO 2 assimilation minus ecosystem respiration), and Net Biome Productivity (NBP = NEP minus carbon losses through disturbances bypassing respiration, e.g. by fire and logging). Based on chronosequence studies and national forestry statistics we estimate a low average NPP for boreal forests in Siberia: 123 gC m –2 y –1 . This contrasts with a similar calculation for Europe which suggests a much higher average NPP of 460 gC m –2 y –1 for the forests there. Despite a smaller area, European forests have a higher total NPP than Siberia (1.2–1.6 vs. 0.6–0.9 × 10 15 gC region –1 y –1 ). This arises as a consequence of differences in growing season length, climate and nutrition. For a chronosequence of Pinus sylvestris stands studied in central Siberia during summer, NEE was most negative in a 67‐y old stand regenerating after fire (– 192 mmol m –2 d –1 ) which is close to NEE in a cultivated forest of Germany (– 210 mmol m –2 d –1 ). Considerable net ecosystem CO 2 ‐uptake was also measured in Siberia in 200‐ and 215‐y old stands (NEE:174 and – 63 mmol m –2 d –1 ) while NEP of 7‐ and 13‐y old logging areas were close to the ecosystem compensation point. Two Siberian bogs and a bog in European Russia were also significant carbon sinks (– 102 to – 104 mmol m –2 d –1 ). Integrated over a growing season (June to September) we measured a total growing season NEE of – 14 mol m –2 summer –1 (– 168 gC m –2 summer –1 ) in a 200‐y Siberian pine stand and – 5 mol m –2 summer –1 (– 60 gC m –2 summer –1 ) in Siberian and European Russian bogs. By contrast, over the same period, a spruce forest in European Russia was a carbon source to the atmosphere of (NEE: + 7 mol m –2 summer –1 = + 84 gC m –2 summer –1 ). Two years after a windthrow in European Russia, with all trees being uplifted and few successional species, lost 16 mol C m –2 to the atmosphere over a 3‐month in summer, compared to the cumulative NEE over a growing season in a German forest of – 15.5 mol m –2 summer –1 (– 186 gC m –2 summer –1 ; European flux network annual averaged – 205 gC m –2 y –1 ). Differences in CO 2 ‐exchange rates coincided with differences in the Bowen ratio, with logging areas partitioning most incoming radiation into sensible heat whereas bogs partitioned most into evaporation (latent heat). Effects of these different surface energy exchanges on local climate (convective storms and fires) and comparisons with the Canadian BOREAS experiment are discussed. Following a classification of disturbances and their effects on ecosystem carbon balances, fire and logging are discussed as the main processes causing carbon losses that bypass heterotrophic respiration in Siberia. Following two approaches, NBP was estimated to be only about 13–16 mmol m –2 y –1 for Siberia. It may reach 67 mmol m –2 y –1 in North America, and about 140–400 mmol m –2 y –1 in Scandinavia. We conclude that fire speeds up the carbon cycle, but that it results also in long‐term carbon sequestration by charcoal formation. For at least 14 years after logging, regrowth forests remain net sources of CO 2 to the atmosphere. This has important implications regarding the effects of Siberian forest management on atmospheric concentrations. For many years after logging has taken place, regrowth forests remain weaker sinks for atmospheric CO 2 than are nearby old‐growth forests.

Cloning and functional analysis of a cDNA encoding a starch synthase from potato ( Solanum tuberosum L.) that is predominantly expressed in leaf tissue - Jens Kossmann; Gernot J. W. Abel; Franziska Springer; James R. Lloyd; Lothar Willmitzer (Planta, 1999)

Heterologous expression of soluble methane monooxygenase genes in methanotrophs containing only particulate methane monooxygenase - John S. Lloyd; Paolo De Marco; Howard Dalton; J. C. Murrell (Archives of Microbiology, 1999)

MONITORING THE TREND OF HARBOR SEALS IN PRINCE WILLIAM SOUND, ALASKA, AFTER THE EXXON VALDEZ OIL SPILL - Kathryn J. Frost; Lloyd F. Lowry; Jay M. Ver Hoef (Marine Mammal Science, 1999)
A bstract We used aerial counts to monitor the trend in numbers of harbor seals, Phoca vitulina richardsi , in Prince William Sound, Alaska, following the 1989 Exxon Valdez oil spill. Repetitive counts were made at 25 haul‐out sites during the annual molt period each year from 1990 through 1997. A generalized linear model indicated that time of day, date, and time relative to low tide significantly affected seal counts. When Poisson regression was used to adjust counts to a standardized set of survey conditions, results showed a highly significant decline of 4.6% per year. Unadjusted counts indicated a slight, but not statistically significant, decline in the number of seals. The number of harbor seals on the trend‐count route in eastern and central PWS has been declining since at least 1984, with an overall population reduction of 63% through 1997. Programs to monitor long‐term changes in animal population sizes should account for factors that can cause short‐term variations in indices of abundance. The inclusion of such factors as covariates in models can improve the accuracy of monitoring programs.

Gender dimorphism in indigenous New Zealand seed plants - C. J. Webb; David G. Lloyd; Lynda F. Delph (New Zealand Journal of Botany, 1999)
The frequent occurrence of gender dimorphism has long been recognised as one of the distinctive features of the New Zealand flora. We list 83 seed plant genera in which gender dimorphism occurs, and document habit, pollination, and dispersal characters for each genus. This means that gender dimorphism is represented in 23% of the genera in the flora; however, not all of these genera are uniformly dimorphic in gender—40% of them include some species or populations that lack gender dimorphism. We estimate that gender dimorphism has arisen autochthonously in 17 of the 83 genera— therefore, gender dimorphism evolved elsewhere in most cases (80%), and was established in New Zealand by subsequent migration. A comparison of the genera in which gender dimorphism occurs with the remainder of the flora shows that gender dimorphism is strongly correlated with fleshy fruits, and with woody habits. No correlation was found between gender dimorphism and pollination mode, perhaps because relatively unspecialised pollination systems are another characteristic feature of the New Zealan flora. Among genera for which gender dimorphism appears to have arisen autochthonously, a liane habit seems to have been a contributing factor, whereas fleshy fruit and pollination mode were not.

Detection of somaclonal variation in garlic ( Allium sativum L.) using RAPD and cytological analysis - M. A. Al-Zahim; B. V. Ford-Lloyd; H. J. Newbury (Plant Cell Reports, 1999)

The influence of personal protection, environmental hygiene and exposure to pesticides on the health of immigrant farm workers in a desert country - J. Gomes; O. L. Lloyd; D. M. Revitt (International Archives of Occupational and Environmental Health, 1999)

Distribution of a 375 bp repeat sequence inAllium (Alliaceae) as revealed by FISH - M. Stevenson; S. J. Armstrong; G. H. Jones; B. V. Ford-Lloyd (Plant Systematics and Evolution, 1999)

Oxidation of 1,1,1-trichloro-2,2-bis(4-chlorophenyl)ethane (DDT) by Alcaligenes eutrophus A5 - Lloyd J. Nadeau; Gary S. Sayler; J. C. Spain (Archives of Microbiology, 1998)

In vivo andin vitro cloning and phenotype characterization of tellurite resistance determinant conferred by plasmid pTE53 of a clinical isolate ofEscherichia coli - J. Burian; Nguyen Tu; L'. Kl'učár; L. Guller; G. Lloyd-Jones; S. Stuchlík; P. Fejdi; P. Siekel; J. Turna (Folia Microbiologica, 1998)

Mapping the geographical distribution of genetic variation in the genus Lens for the enhanced conservation of plant genetic diversity - M. E. FERGUSON; B. V. FORD‐LLOYD; L. D. ROBERTSON; N. MAXTED; H. J. NEWBURY (Molecular Ecology, 1998)
Plant genetic resource conservation strategies, informed by an understanding of the geographical distribution of genetic variation within species, are likely to result in a wider representation of conserved diversity in ex situ gene banks and in situ genetic reserves. The main objective of this study was to map the geographical distribution of genetic variation, as revealed by randomly amplified polymorphic DNA (RAPDs), in four wild relatives of the cultivated lentil, namely Lens culinaris ssp. orientalis, L. odemensis, L. ervoides and L. nigricans . Areas of high diversity and unique diversity were located for each taxon, and regions where further germplasm collection was most likely to yield novel genetic variation were identified. There were centres of diversity for L. culinaris ssp. orientalis in southeast Turkey and northwest Syria, and in south Syria and Jordan. A centre of diversity was found to exist in Sweida province, south Syria, for L. odemensis , and for L. ervoides along the coastal border region between Syria and Turkey stretching down along the Syrian coast. There was a centre of diversity for L. nigricans in west Turkey. Analytical techniques previously used at the species level were found to be useful at the genotypic level to objectively target areas for future collection missions, to increase diversity in ex situ collections and to target areas for in situ conservation.

Comparative Analysis of Crossover Exchanges and Chiasmata in Allium Cepa × Fistulosum After Genomic In Situ Hybridization (GISH) - M. Stevenson; S. J. Armstrong; B. V. Ford-Lloyd; G. H. Jones (Chromosome Research, 1998)

Mechanisms of orthopyroxene dissolution in silica-undersaturated melts at 1 atmosphere and implications for the origin of silica-rich glass in mantle xenoliths - Cliff S. J. Shaw; Yves Thibault; Alan D. Edgar; Felicity E. Lloyd (Contributions to Mineralogy and Petrology, 1998)

6-hydroxydopamine lesion of rat nigrostriatal dopaminergic neurons differentially affects nicotinic acetylcholine receptor subunit mRNA expression - Kathryn J. Elliott; Jay M. Jones; Aida I. Sacaan; G. Kenneth Lloyd; Janis Corey-Naeve (Journal of Molecular Neuroscience, 1998)

Peroxidase-Catalyzed Oxidation of 2,4,6-Trichlorophenol - F. W. Wiese; H. C. Chang; R. V. Lloyd; J. P. Freeman; V. M. Samokyszyn (Archives of Environmental Contamination and Toxicology, 1998)

Movements and behavior of satellite-tagged spotted seals ( Phoca largha ) in the Bering and Chukchi Seas - Lloyd F. Lowry; Kathryn J. Frost; Randall Davis; Douglas P. DeMaster; Robert S. Suydam (Polar Biology, 1998)

Characterization of a mouse monoclonal IgG3 antibody to the tumor-associated globo H structure produced by immunization with a synthetic glycoconjugate - Valery Kudryashov; Govindaswami Ragupathi; In Jong Kim; Michael E Breimer; Samuel J Danishefsky; Philip O Livingston; Kenneth O Lloyd (Glycoconjugate Journal, 1998)

Exclusion of ZFM1 as a candidate gene for multiple endocrine neoplasia type 1 (MEN1) - S. E. Lloyd; J. T. Pang; S. H. S. Pearce; S. E. A. Leigh; R. V. Thakker (Human Genetics, 1997)

Formate utilization by members of the genus Methanobacterium - J. Benstead; D. B. Archer; D. Lloyd (Archives of Microbiology, 1991)

Respiration of the hydrogenosome-containing fungus Neocallimastix patriciarum - N. Yarlett; C. Rowlands; J. C. Evans; D. Lloyd (Archives of Microbiology, 1987)

Determination of the DDE and PCB contents of peregrine Falcon eggs: A comparison of whole egg measurements and estimates derived from eggshell membranes - David B. Peakal'; Thomas S. Lew; Alan M. Springer; Wayman Walker IP; Robert W. Risebrough; J. Geoffrey Monk; Walter M. Jarman; Brian J. Walton; Lincoln M. Reynolds; Richard W. Fyfe; Lloyd F. Kiff (Archives of Environmental Contamination and Toxicology, 1983)

Acute toxicity of hydrogen cyanide to freshwater fishes - Lloyd L. Smith; Steven J. Broderius; Donavon M. Oseid; Gary L. Kimball; Walter M. Koenst (Archives of Environmental Contamination and Toxicology, 1978)

Management and its effect on the incidence of bacterial wilt in two Potato-growing areas on the Northern Tablelands of New South Wales. - AB Lloyd; MN Shamsuddin; J Praed (Australasian Plant Pathology, 1974)

Esterase activity of Aspergillus niger in continuous culture - A. M. L. Ng; G. I. Lloyd; J. E. Smith (Archives of Microbiology, 1974)